Enhancing solid-state hydrogen storage via integrating helical coil heat exchanger with sandwiched phase change materials - Puyang Lu; Mingjie Lai; Rui Zhou; Zhuofan Chen; Haichen Yao; Zhi Li; Fanjun Deng; Xianglei Liu (Fuel, 2027)

Seasonal dynamics of geogenic phosphorus in alluvial-lacustrine aquifers: Coupling of phosphorus-containing dissolved organic matter and microbes as a key driver - Junna Ning; Yao Du; Baisong Deng; Mengze Li; Tianming Wu; Lijie Lin; Taiping Yu; Yiqun Gan; Dandan Si; Wen Zhang; Yanxin Wang (Water Research, 2027)

Associations of low-level multi-metal exposure with peripheral blood-based inflammatory indices and the mediating role of gut microbiota: evidence from lifestyle-standardized men - Yao Wang; Tao Lin; Xudong Zhang; Ke Li; Zixin Guo; Erxian Li; Xinwei Wu; Yongxian Li; Degang Wu; Qifei Deng; Peng He (Environmental Research, 2026)

A Neoproterozoic arc-backarc system in the northern Yangtze Block: Implications for crustal growth and Rodinia reconstructions - Chao Chen; Hao Deng; Jin-Ling Yuan; Timothy Kusky; Qiang Chen; Zhen-Bing She; Ling-Yao Kong; Jiang Zhu; Hong-Mei Li; Jing-Meng Huang; Guo-Hu Wang; Cheng Yang; et al. (Earth-Science Reviews, 2026)

A deep learning and generative modeling pipeline for mining and engineering alkaline-stsable xylanases - Ruohan Zhang; Yiyang Zhang; Zhonghao Deng; Pengtao Wang; Lingxi Fan; Feng Guo; Huiying Luo; Yuan Wang; Tao Tu; Bin Yao; Jian Tian; Huoqing Huang; et al. (Bioresource Technology, 2026)

Lower crustal modification at the margin of the North China Craton: Multi-proxy geochemical and isotopic imaging constraints from the Late Mesozoic granitoids in Jiaodong Peninsula - Can-Can Wang; Li-Qiang Yang; Xue Gao; Wen-Yan He; Lei Ju; Dong Xie; Long Wang; Shi-Yao Zhai; Wei Yang; Nan Li; Zheng-Jiang Ding; Jun Deng (Journal of Asian Earth Sciences, 2026)

Inhibition of biogenic amine formation in the Pseudomonas fluorescens quorum sensing system via PVA/CMS films loaded with HNTs-lycopene/phytol - Hongwei Zhan; Weiwei Zhang; Xiang Zou; Shaomei Li; Hongting Chu; Yao Wang; Yingming Sun; Guanyuan Qu; Lixiu Zhang; Jinsheng Shi; Xiaoying Kong; Yang Deng; et al. (International Journal of Food Microbiology, 2026)

InSAR-derived surface deformation and numerical simulation: constraints on the seismogenic fault and rupture process of the 2021 MS 5.4 Baicheng earthquake - Hanxiao Deng; Zhenyun Wu; Keyi Mao; Yuan Yao; Fengnian Chang; Shaochun Dong; Changsheng Li; Fei Xia; Hongwei Yin (Geomorphology, 2026)

Dehydroacetic acid disrupts cold adaptation and biofilm formation in Pseudomonas lundensis: A targeted strategy for enhancing microbiological safety of refrigerated poultry - Yanqing Li; Yaxin Lu; Zhijun Zhang; Weiwei Zhang; Wenhui Wang; Kai Xu; Xinyu Zhang; Lixiu Zhang; Guanyuan Qu; Jingyuan Li; Qianru Chen; Tiejun Chen; et al. (Food Microbiology, 2026)

Unmanned aerial vehicle infrared thermography for building inspection: A systematic review from 2D, 3D, temporal, and cross-scale perspectives - Linghan Yao; Yuwen Deng; Qiyi Li; Zihan Yang; Wei Wang (Energy and Buildings, 2026)

Autothermal pyrolysis of traditional Chinese medicine residues for the sustainable products: Oxygen boundary, coupled kinetics, and product valorization - Qian Deng; Aijun Li; Yongda Huang; Yuxin Wang; Chao Liao; Yicheng Lei; Yuanyu Zhu; Yulu Fan; Hong Yao (Chemical Engineering Journal, 2026)

Endoplasmic reticulum stress is involved in chronic chlorpyrifos-induced jejunal barrier injury in weaned mice - Junkang Zhao; Yue Zhang; Jinyu Li; Yuli Zhu; Xunuo Song; Yao Meng; Yuming Zhang; Qinghua Deng; Liyin Du (Chemico-Biological Interactions, 2026)

Herbal residue treatment and return-to-field application: life cycle assessment combined with economic, thermodynamic, and ecological analysis - Qian Deng; Aijun Li; Haoyu Tang; Yongda Huang; Chao Liao; Lianming Du; Yuanyu Zhu; Hong Yao (The International Journal of Life Cycle Assessment, 2026)

Dissolved inorganic phosphorus enrichment in groundwater of phosphate mining areas driven by multiple biogenic pathways - Junna Ning; Yao Du; Tianming Wu; Mengze Li; Baisong Deng; Wen Zhang; Yiqun Gan; Haomiao Yang; Xiaoxia Chen; Rui Ma; Yanxin Wang (Water Research, 2026)

P-wave velocity structure of the Zhongnan Fault and Ridge Zone between two sub-basins of the South China Sea - Wang Li; Chun-Feng Li; Yongjian Yao; Min Xu; Chuanhai Yu; Yongkang Deng; Ming Yang; Jinwei Gao (Tectonophysics, 2026)

Platform-scale variability of Aeronian (early Silurian) δ13Ccarb excursions in the South China Block and its implications - Shenyang Yu; Zhongyang Chen; Stephen Kershaw; Lin Na; Shouxiang Wang; Shasha Liu; Yutao Wang; Yao Wang; Yingyan Mao; Xiaojie Deng; Qijian Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

“Lotus leaf meets nacre”: a dual biomimetic approach to creating highly humidity-stable films with exceptional barrier properties for food packaging - Ningkang Deng; Jinsong Zeng; Pengfei Li; Junzhang Wu; Jianqiao Su; Zhiqiang Gong; Yuan Peng; Ting Yao; Jinpeng Li; Daxian Cao; Bin Wang; Jun Xu; et al. (Food Chemistry, 2026)

Characteristics and Ozone Formation Risk of VOCs Emission in the Railway Equipment Maintenance and Repair Industry - Hongbing Zhao; Tianxue Yang; Xiaowei Wang; Shihai Deng; Dongyang Li; Zhiliang Yao; Zhifeng Hu; Dayang Yu; Dongxiao Sun; Zhiqiang Dong; Jianfei Liu (Water, Air, & Soil Pollution, 2026)

Retraction notice to “Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China” [Sci. Total Environ. 897 (2023) 165394] - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2026)

Solving excited states for long-range interacting trapped ions with neural networks - Yixuan Ma; Chang Liu; Weikang Li; Shun-Yao Zhang; Lu-Ming Duan; Yukai Wu; Dong-Ling Deng (Science Bulletin, 2026)

Was the magma redox of the West Kunlun Paleo-Tethys modulated by surface environmental conditions of the Late Paleozoic Ice Age? - Zong-Yong Yang; Jing-Jing Zhu; Ruizhong Hu; Xian-Wu Bi; Li-Chuan Pan; Xing-Chun Zhang; Ju-Ting Deng; Yao-Wen Zhang; Qian Liu; Yi-Xin Li (Global and Planetary Change, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Impact and evaluation of different temporal compositing strategies on the accuracy of tea plantation remote sensing mapping - Deng Zhi-Yong; Wu Guo-Hui; Liu Xiao-Jing; Yang Ya-Jie; Luo Jian; Zhang Hai-Yao; Du Xin-Lu; Li Ting; Wang Shan (International Journal of Remote Sensing, 2026)

Anthropogenic Warming Increases Extreme Precipitation in Huaihe River Basin, China in 1961–2020 - Hongtao Guo; Chang Li; Jiping Zhang; Hongliang Du; Qingquan Li; Xinyong Shen; Tiejun Xie; Haoxin Yao; Xueliang Deng; Liang Zhao (International Journal of Climatology, 2026)
The Huaihe River basin (HRB) is highly susceptible to extreme precipitation disasters and has a high risk of flooding. However, there is currently a lack of quantitative analysis and mechanistic explanation regarding the impact of anthropogenic greenhouse gas emissions on extreme precipitation in the HRB. Here we investigate the impact of greenhouse gas emissions on the total precipitation when precipitation exceeds the 95th percentile (R95p) over the HRB. And explore the underlying causes by using observational data in conjunction with greenhouse gas‐forced and natural‐forced experiment data from the CMIP6 program. In 1961–2020, summer average R95p over the HRB has increased by 26.21%. In the selected CMIP6 models, the greenhouse gas forcing experiment found a faster increase in R95p than the natural forcing experiment. The CMIP6 model data indicates that extreme precipitation years in the greenhouse gas forcing experiment increase by 57.14% compared with the natural forcing experiment. Further analysis indicates that anthropogenic greenhouse gas emissions have led to an uneven reduction of spring snow cover in northern Asia and sea ice cover in the Arctic, resulting in an increase in summer blocking events over the eastern Ural Mountains. This enhances the dynamic and thermal conditions of precipitation in the HRB, making it more conducive to extreme precipitation events. These findings contribute to a deeper understanding of the mechanisms by which greenhouse gas emissions influence regional extreme precipitation and have significant implications for long‐term forecasting of extreme precipitation events in the HRB.

Dietary lipid sources modulate low-salinity adaptation in Scylla paramamosain via integrated multi-omics and AQP1/AQP7 regulation - Tiantian Xu; Xiaoyue Li; Yao Deng; Shichao Xie; Wenhao Zhan; Xishuai Cui; Binjie Zhou; Wenli Zhao; Tingting Zhu; Peng Sun; Min Jin; Qicun Zhou (Marine Life Science & Technology, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Molecular-level fractionation and transformation of dissolved organic matter by schwertmannite during photo-aging: Implications for the carbon cycle in acid mine drainage environments - Qian Yao; Junchun Li; Zhenxing Zhang; Xiaohu Jin; Xiaofei Li; Changdong Ke; Yirong Deng; Guining Lu; Chuling Guo; Zhi Dang; Xiaoyun Yi (Journal of Hazardous Materials, 2026)

Fluid evolution and petroleum accumulation in the Middle Permian gas reservoirs of the Sichuan Basin, China - Yun Liao; Jianyong Zhang; Zeqi Li; Heng Wang; Juan Wu; Genshun Yao; Wenzheng Li; Feng Liang; Shugen Liu; Bin Deng (Journal of Asian Earth Sciences, 2026)

Phyllanthus emblica L. polyphenols mitigate high-fat diet-induced cognitive impairment via modulating gut microbiota and calcium/cAMP signaling pathways - Xinyi Deng; Ziyuan Li; Jiamin Tian; Fang Chen; Zeyuan Deng; Qirui Hu; Xiaoya Wang; Le Kang; Zhihong Zhang; Yao Pan (Food Bioscience, 2026)

A multi-functional passive fixation lead for diagnosis and treatment of cardiac diseases - Xuandi Deng; Yiran Hu; Puqing Yao; Chunhong Yu; Juwei Yang; Ruizeng Luo; Sijing Cheng; Hao Huang; Peng Cheng; Lei Jia; Xingyao Lv; Menghan Li; et al. (Chemical Engineering Journal, 2026)

Field Study of Immobilization Materials and Foliar Inhibitors: Balancing Rice Yield, Safety, and Economy in Cd-As Contaminated Soils - Junchun Li; Longyong Lin; Yirong Deng; Sheng Cheng; Xiao Yang; Xiulan Yan; Qian Yao; Cunliang Han (Water, Air, & Soil Pollution, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Pre-molt cholesterol regulation of ecdysone receptor (EcR) signaling in the Y-organ contributes to dietary control of molting in Scylla paramamosain - Shichao Xie; Yao Deng; Yinqiu Tian; Zheng Tang; Tiantian Xu; Xiaoyue Li; Wenhao Zhan; Hongyu Peng; Yangguang Bao; Tingting Zhu; Wenli Zhao; Min Jin; et al. (Insect Biochemistry and Molecular Biology, 2026)

Amelioration of NAFLD by herbal-dairy meal replacement (HD-MR) potentially via the gut microbiota–short-chain fatty acid axis - Yuqing Xie; Qirui Hu; Zhiqing Gong; Chuxian Li; Jinrong Yang; Pinnan Zhang; Fengxin Wang; Yao Pan; Zeyuan Deng; Fang Chen (Food Bioscience, 2026)

Microplastic entry into bloodstream via hemodialysis: A dual-simulation clinical study - Yao Deng; Taoping Sun; Zhenheng Long; Xiaoling Luo; Xuyang Geng; Zefang Lin; Chunzhao Chen; Xiaoliang Li (Environmental Pollution, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Contrasting land-use sources of microplastic and endocrine-disrupting compound pollution in a major coastal river network - Weimin Yao; Juan-Ying Li; Bangping Deng; Jie Yin; Jingxi Li; Jiawei Kang; Xin Wang; Nicholas J. Craig; Lei Su (Marine Pollution Bulletin, 2026)

Soil stoichiometric C/N and nitrogen availability jointly shape fungal and bacterial necromass carbon accumulation across ecosystems - Baorong Wang; Deng Ao; Chao Liang; Kate Buckeridge; Chunhui Liu; Yang Yang; Yao Li; Huijun Li; Zhongming Wen; Shaoshan An (Soil and Tillage Research, 2026)

Efficient paired indirect electrosynthesis of adipic acid from phenol using polyoxometalate electrolytes - Wensi Tang; Zhongling Lang; Ruiqi Yao; Tianyu Qiu; Yonghui Wang; Huaqiao Tan; Wei Liu; Zhen Sun; Zhichao Sun; Yingqi Li; Yangguang Li; Yulin Deng (Science Bulletin, 2026)

A semi-supervised deep learning framework based on multi-source data for wheat: from counting to yield estimation - Qing Geng; Xin Xu; Xinming Ma; Fan Xu; Jiayue Yu; Xiaoqiang Yang; Yupeng Deng; Diyou Liu; Li Li; Bingbo Gao; Yu Meng; Jianyu Yang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Quantifying infectious murine norovirus 1 in heat-processed seaweed - Shijue Gao; Hui Li; Qingwei Deng; Gloria Sánchez; Xuejun Ma; Hong Yao; Xiyang Wu (Food Research International, 2026)

Unraveling spatiotemporal dynamics of dissolved organic phosphorus in an urban lake using FT-ICR MS and fluorescence spectroscopy - Mengze Li; Yao Du; Tianming Wu; Xinrui Jiang; Baisong Deng; Junna Ning; Dandan Si; Yiqun Gan; Qinghua Liu; Luyi Huang (Environmental Research, 2026)

Structural analogs TOCP and TPHP induce immunotoxicity in zebrafish through divergent disruption of energy metabolism - Xinyan Li; Dongmei Lai; Yao Yao; Jiewei Deng; Lijuan Luo; Xiaoping Liang; Tiangang Luan (Environmental Pollution, 2026)

Balancing the structural order–redox chemistry via lithium content for stable layered oxide cathodes - Hao Liu; Yongjian Li; Bijian Deng; Hang Li; Weibo Hua; Deniz Wong; Wei Xiang; Yao Xiao; Michael Knapp; Helmut Ehrenberg; Sylvio Indris (Chemical Engineering Journal, 2026)

Electron buffering by carbon dots enhances H2 activation and selective aldehyde hydrogenation over Cu/Al2O3 catalysts - Feifei Mei; Chenyang Shen; Mingyang Deng; Jun Yao; Yue Huang; Fengfeng Li; Mingyang Deng; Xuefeng Guo; Weiping Ding (Chemical Engineering Journal, 2026)

Characterisation and meiotic observation of triploid hybrids of Ipomoea trifida (2x) and Ipomoea tabascana (4x) by reciprocal crosses - Zongkuan Weng; Lukuan Zhao; Jiangong Li; Yao Wang; Yitong Deng; Lingxiao Zhao; Shizhuo Xiao; Tianni Yang; Xibin Dai; Zhilin Zhou; Qinghe Cao (Planta, 2026)

Synergistic effects of volatile interactions on the pyrolysis gas and aromatic hydrocarbons formation during multi-component medical waste pyrolysis - Chao Liao; Aijun Li; Yongda Huang; Muhammad Usman; Yuhang Zheng; Qian Deng; Yicheng Lei; Hong Yao (Process Safety and Environmental Protection, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Assembling a complete metabolic pathway enables Escherichia coli to acquire naphthalene bioremediation ability - Bo Wang; Yu Wang; Qin Yang; Lijuan Wang; Jianjie Gao; Jing Xu; Zhenjun Li; Cen Qian; Yongdong Deng; Wenhui Zhang; Yongsheng Tian; Rihe Peng; et al. (Journal of Environmental Chemical Engineering, 2026)

A wholly coherent wireless energy storage and sensing microsystem toward flexible wearable electronics - Qing You; Chang Gao; Mingjian Pan; Tongkun Wei; Weihe Shen; Xuan Yao; Hanyu Wang; Yuning Li; Xue Li; Jingye Sun; Mingqiang Zhu; Tao Deng (Chemical Engineering Journal, 2026)

Thermal runaway behaviour induced by localised aluminium-water reaction at low temperature - Hai-Fang Mao; Jia-Wei Fang; Yi-Kang Deng; Jun Zhang; Yan-Li Zhao; Yao Feng; Min Xiong; Hui-Ting Gu; Xiao Feng; Jian-Hao Fang; Jian-Hua Chen; Chi-Min Shu; et al. (Chemical Engineering Journal, 2026)

Flow-induced shear enhancement of dynamic lubrication surfaces for combating complex biofouling in biliary stents - Jiaxin Liu; Junchang Guo; Wei Liu; Han Yao; Linjie Guo; Yuan Gao; Bingyang Lu; Luohuizi Li; Huali Yu; Jing Luo; Liansong Ye; Xu Deng; et al. (Chemical Engineering Journal, 2026)

A Real-World Disproportionality Analysis of Drug-Induced Heart Failure: Integrating FAERS Database and AHA Statement - Da Li; Yidan Dong; Lei Yao; Xiaozhe Chen; Yunfeng Li; Xiaohong Deng; Jianhua Li; Mingzhu Wang; Deyu Fu (Cardiovascular Toxicology, 2026)

Effect of temperate phage SapYZUs891 as a biocontrol agent on the Chinese foodborne multidrug-resistant Staphylococcus aureus isolates - Xiaoxing Fan; Zhilan Yao; Yuhong Wu; Wenjuan Li; Yeling Han; Xuan Li; Aiping Deng; Guoqiang Zhu; Zhenquan Yang; Wenyuan Zhou (Archives of Microbiology, 2026)

Thermodynamic and economic analyses of a novel SOFC-CCES system based on CO2 separation without energy consumption - Hongsheng Zhang; Hanlin Li; Yipeng Zhang; Changfu Deng; Yao Wu; Chenghong Duan; Manman Qiao; Jiyun Qin (Fuel, 2026)

Zinc leaching from low-grade oxide ores in NH3-(NH4)2CO3 medium: Thermodynamics, kinetics, and process analysis - Qiyou Chen; Jinlei Yang; Baohua Sun; Shiyan Wu; Bingjie Jin; Yuhui Zhang; Wenkai Liang; Xian Zhong; Longyu He; Ruixue Yang; Dong Li; Yao Deng (Chemical Engineering Journal, 2026)

Determining the source contributions of dissolved organophosphorus compounds in lake water utilizing FT-ICR-MS and PCA-APCS-MLR receptor models - Xinrui Jiang; Yao Du; Mengze Li; Rui Xu; Tianming Wu; Baisong Deng; Dandan Si; Wen Zhang; Jingwen Yu; Yanxin Wang (Journal of Hydrology, 2026)

Predicting and classifying deoxynivalenol in wheat flour using ATR-FTIR spectroscopy and explainable machine learning - Jiajun Liu; Kebing Yao; Chen Chen; Dongsheng Li; Dengan Xu; Rui Guo; Weicheng Yao; Yao Deng; Wenting Xue; Qinyan Wu; Tao Li; Xinyao He; et al. (Journal of Hazardous Materials, 2026)

Valorisation of medical waste through the staged pyrolysis: effect of pyrolysis conditions on chlorine removal and product formation - Yuhang Zheng; Tong Zhang; Aijun Li; Yongda Huang; Muhammad Usman; Qian Deng; Chao Liao; Yi Huang; Hong Yao (Fuel, 2026)

A novel polyphenol-metal chelation-based structure enabling epoxy with outstanding flame retardancy, toughening effect, smoke suppression performance and recyclability - Yao Deng; Hang-Ping Fang; Qing-Qing Bi; Ying-Ming Li; De-Yi Wang (Chemical Engineering Journal, 2026)

Tunable ether-functionalized protic ionic liquid for efficient glycolysis of polyethylene terephthalate - Lulu Deng; Yao Meng; Zhonghao Chen; Xinrui Li; Lei Wang (Chemical Engineering Journal, 2026)

Low-dose astaxanthin promotes growth via bile acid-regulated metabolic and lipid-antioxidant pathways in Scylla paramamosain - Yao Deng; Shichao Xie; Wenhao Zhan; Tingting Zhu; Hongyu Peng; Haiqing Cao; Zheng Tang; Xiaoyue Li; Tiantian Xu; Min Jin; Qicun Zhou (Aquaculture, 2026)

Early Triassic tectonic inversion in South China linked to the oblique closure of the Paleo-Tethys Mianlue Ocean - Qiang Xu; Wei Deng; Chunyuan Gu; Yu Cao; Xiucheng Tan; Ling Li; Bing Luo; Zhanfeng Qiao; Yibo Li; Yao Xie; Stephen Kershaw (Tectonophysics, 2026)

Time-varying disturbance estimation via backstepping observer: A paradigm shift for precision control of marine optoelectronic turntables - Jiachen Li; Shanlin Zhuang; Jiuqiang Deng; Feng Shen; Yao Mao (Ocean Engineering, 2026)

Three-dimensional shear-wave velocity structure of the longnan geothermal field in the Central Jiulianshan uplift derived from seismic ambient noise tomography - Ronghua Xu; Juzhi Deng; Cheng Li; Huajian Yao; Yang Gao; Zequn Wen (Journal of Applied Geophysics, 2026)

CO2 adsorption capture for heavy duty trucks: Performance analysis and standardized evaluation - Yujia Pang; Chenxi Jia; Wanyang Li; Weiwei Meng; Lixin Yao; Xisheng Zhang; Jialin Li; Zhiqiang Huang; Shuai Deng (Fuel, 2026)

Genomic, transcriptional and proteomic clarification of fathead minnow and common carp composition in epithelioma papulosum cyprini (EPC) cell line - Bo Li; Jing Hao Yuan; Yu Hang Deng; Shan Nan Chen; Meng Yao Ji; Xu Jia Zhang; Yang Liu; Zhen Gan; Pin Nie; Lan Hao Liu (Fish & Shellfish Immunology, 2026)

Maternal exposure to indoor and outdoor air pollution during pregnancy increases offspring risk of autism spectrum disorder - Lingxi Wang; Wei Li; Yunchong Yao; Xiufang Jiang; Dongmei Ma; Yinxia Liu; Yunhua Deng; Lijiao Sun; Hong Li; Yuping Zhao; Guangyang Peng; Guo Wei; et al. (Environmental Research, 2026)

Mechanisms and model performance evaluation of evapotranspiration partitioning in summer maize in Northwest China - Yao Li; Xuegui Zhang; Zengxuan Deng; Xuanang Liu; Xiaobo Gu; Jiatun Xu; Lianyu Yu; Huanjie Cai; Xiongbiao Peng (European Journal of Agronomy, 2026)

Enhancement of microalgal carbon fixation via synergistic interactions with a facultative autotrophic bacterium Cytobacillus KQ-2 - Dandan Yao; Yunhui Li; Zhiqian Han; Ding Tan; Meng Wang; Huan Deng; Hui Wang; Yun Liu (Bioresource Technology, 2026)

Divergences in typhoon and non-typhoon extreme rainfall trends and their spatial variations at multiple timescales in typical region of southeastern China - Senzhen Wang; Weifang Ruan; Xiaocheng Li; Huaxia Yao; Haijun Deng; Chunqiang Li; Xingwei Chen (Atmospheric Research, 2026)

Sewage surveillance revealed the emergence and prevalence of human rhinovirus and human parainfluenza virus in China based on their fecal shedding rates - Xin Du; Yao Deng; Hongxia Ming; Haifeng Li; Chunlong Zhu; Fenglan He; Songzhe Fu (Water Research, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Deep banding of controlled-release potassium chloride increases soybean productivity by regulating microbial communities and improving potassium uptake - Zhaoming Qu; Qin Wang; Hao Deng; Qianhui Chen; Hui Dong; Shuihong Yao; Chengliang Li (Soil and Tillage Research, 2025)

Tree-mycorrhizal types differ in their biomass response to nitrogen addition - Guoyin Chen; Yuanliu Hu; Jianping Wu; Richard P. Phillips; Jianyang Xia; Ying-Ping Wang; Dafeng Hui; Jianling Li; Xianyu Yao; Qi Deng (Soil Biology and Biochemistry, 2025)

Experimental and numerical investigation of droplet splitting dynamics at X-shaped fracture intersections - Cao Luo; Zhiping Deng; Chi Yao; Shuanglong Li; Chuang-Bing Zhou (Journal of Hydrology, 2025)

A flexible bionic bimodal sensor with distinguishing temperature and humidity signals - Xuan Yao; Chang Gao; Mingjian Pan; Tongkun Wei; Weihe Shen; Qing You; Hanyu Wang; Jingru Peng; Danke Chen; Xiaoqiu Tang; Xue Li; Yuning Li; et al. (Chemical Engineering Journal, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Synergistic co-pyrolysis characteristics of waste tire and moso bamboo: Mechanisms and kinetics - Nan Deng; Yunlong Ye; Xiaolong Yao; Zijun Ren; Qi Zhang; Bin Li; Lingjie Meng (Chemical Engineering Journal, 2025)

Cutting Efficiency and Microdamage in Hard Rocks Under Repeated Abrasive Water Jet Cutting - Zhe Zhou; Zhi Yao; Zhaolong Ge; Zhongtan Li; Jianming Shangguan; Yuhuai Cui; Binbin Ge; Qinglin Deng (Rock Mechanics and Rock Engineering, 2025)

Estimating microbial necromass contribution to mineral-associated organic matter: comparison of stoichiometric and biomarker methods - Yiren Zhu; Yuanliu Hu; Xianyu Yao; Guoyin Chen; Junbing Bai; Jianling Li; Deqiang Zhang; Qi Deng (Plant and Soil, 2025)

Plant–soil feedback alters plant–soil–microbial nutrient status and elemental-limitation status during secondary succession - Yong Cao; Zemin Ai; Xinghua Li; Mengjia Hou; Yuyan Yao; Yi Deng; Huan Liu; Jiaoyang Zhang; Guobin Liu; Sha Xue (Soil Ecology Letters, 2025)

The CMA Global Atmospheric Reanalysis Version 1.5 (CRA1.5) - Tao Zhang; Zijiang Zhou; Zhiquan Liu; Chunxiang Shi; Shuang Yao; Lipeng Jiang; Yan Yao; Zhisen Zhang; Xiao Liang; Zhiqiang Zhang; Junxia Gu; Jie Liao; et al. (Journal of Meteorological Research, 2025)

Field synergy enhancement of fluid flow and heat transfer in intensive tobacco roasting room - Sheng Tang; Jun Zhong; Ming Li; Yonglei Jiang; Ying Zhang; Jianhuan Deng; Chen Deng; Zhihan Deng; Muchi Yao (Computers and Electronics in Agriculture, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Carbon isotope stratigraphy of early Silurian carbonate rocks from the South China Block: Implications for dating post-Ordovician reef recovery - Shenyang Yu; Shouxiang Wang; Zhongyang Chen; Stephen Kershaw; Axel Munnecke; Shasha Liu; Xiaojie Deng; Wei Guo; Yingyan Mao; Yao Wang; Qijian Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Spatial and temporal variability in molecular characteristics of dissolved organic matter in a large freshwater lake: A case from the Dongting Lake, central China - Rui Xu; Yao Du; Tianming Wu; Xinrui Jiang; Baisong Deng; Mengze Li; Yiqun Gan; Mengjie Song; Shaobo Liao; Rui Zhang; Yanxin Wang (Journal of Hydrology, 2025)

Predictive modeling of antioxidant synergies in fruits and vegetables: A multi-objective optimization approach for functional food design - Xia Wang; Shiyu Zou; Hongan Li; Zeyuan Deng; Yao Pan; Hongyan Li (Food Chemistry, 2025)

Shear behavior of RC composite beams with HDC permanent formwork: Experimental study and PINN-based prediction - Zhengtao Qiu; Mingke Deng; Xin Yao; Yangxi Zhang; Ruizhe Li (Engineering Structures, 2025)

Regulating the charge transport ability of the TiO2/CsPbI2Br perovskite interface layer by MoS2 nanoparticles for high-performance carbon-based all-inorganic perovskite solar cells - Zhaowei Huang; Lin Gao; Fengli Liu; Shihui Xu; Yaxuan Chai; Jing Li; Qing Yao; Haozhen Deng; Liuxue Sun; Jihuai Wu; Zhang Lan (Chemical Engineering Journal, 2025)

Differences in temporal patterns of bacterial community assembly between soybean rhizosphere and endosphere - Ting Jin; Shuanghui Wang; Yong Wu; Junyao Deng; Xuanjing Li; Yao Liu; Jianli Zhang; Wuxuan Li; Gehong Wei; Peng Shi (Applied Soil Ecology, 2025)

Surficial sedimentary properties of Makran accretionary prism and its application to natural gas hydrate distribution - Haifeng Wang; Liang Yi; Fenlian Wang; Yibing Li; Yun Cai; Zhen Zhang; Miao Yu; Xianze Deng; Yong Yang; Huiqiang Yao; Xiguang Deng; Gaowen He (Frontiers in Marine Science, 2025)
The Makran accretionary prism (MAP) resulted from the low-angle, slow-rate subduction of the Arabian Plate beneath the Eurasian Plate. The MAP is an active continental margin, with natural gas hydrate (NGH). In this study, we report an integrated study on surficial sediments, in terms of sediment grain-size, clay minerals and elements. The main results are as follows: (1) the surficial sediments were mainly controlled by hydrodynamic conditions of the Indus River. Along the Indus River channel, it is mainly infilled with silt, while clays are mainly distributed in the accretionary prism. The turbidity records gradually decrease from east to west, along the Indus River channel. (2) Illite and chlorite are the dominate clay minerals, indicating that the surficial sediments were mainly from weathering processes in the Himalaya by the Indus River transport. The very-low contents of kaolinite and smectite indicate the lack of sediments from the Deccan Traps and the in situ hydrothermal materials. (3) Elements analysis indicates that elements Al, Mg, K, Fe, and Ti were terrigeneous, mainly distributed in the northern MAP, while elements Ca and P were from biogenic sources, mainly distributed in the southern part of the study area. In addition, elements U and Mo distribute generally coupled with bottom simulating reflector (BSR), which can be used as proxies of NGH identification. Therefore, we proposed that the covariation between NGH distribution, BSR identification, and trace elements Mo and U holds the potentials in NGH investigation.

Coupled effects of riverbed topography and entrainment probability on bedload transport in the Middle Yangtze River - Linlin Li; Yu Lei; Junqiang Xia; Meirong Zhou; Shanshan Deng; Yao Xiao; Hang Li; Maohua Le (Acta Geophysica, 2025)

Development of a nondestructive prediction model for nutrient content of orchid leaves using different hyperspectral sensors - Shuwen Deng; Lu Chen; Qingnv Li; Yao Feng; Chengfeng Li; Shuang Li; Shasha Wu; Junwen Zhai (Computers and Electronics in Agriculture, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Characteristics of atmospheric reduced-sulfur compounds at a suburban site of Shanghai - Kai Deng; Juntao Huo; Yuwei Wang; Lihong Wang; Sijia Yin; Chuang Li; Yueyang Li; Gan Yang; Lei Yao; Qingyan Fu; Lin Wang (Journal of Environmental Sciences, 2025)

Integration of metabolomics and transcriptomics unravels the molecular mechanisms underlying variations in flavor-related volatiles in Citrus reticulata ‘Chachi’ grafted onto different rootstocks - Ding Huang; Jinmei Li; Yuping Wei; Xiang Luo; Xin Xie; Jianhua Chen; Shaochang Yao; Liangbo Li; Jialing Fu; Jidi Xu; Chongling Deng; Rongshao Huang; et al. (Food Research International, 2025)

Biomass-derived organic aerogels endowed flexible polyurethane foam with excellent flame retardance, smoke suppression, bacteriostasis and enhanced mechanical property - Ying-Ming Li; Yao Deng; Hang-Ping Fang; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2025)

Modification effects of regional temperature and humidity on the relationship between daily mortality and short-term coexposure to fine particulate matter and ozone - Jing Zeng; Jian Qian; Jiayi Chen; Sheng Li; Junyu Wang; Menghan Yao; Qianqian Du; Na Yang; Tao Zhang; Fei Yin; Chenglin Tao; Xinyin Xu; et al. (Atmospheric Environment, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

The impact of land leasing strategies on industrial green total factor productivity: Insights from Chinese cities - Shurong Yao; Haiwei Li; Zhongqi Deng (Land Use Policy, 2025)

Precision hydrogen detection in mixed atmospheres using temperature-modulated PdAu-In2O3 sensor arrays and machine learning algorithms - Long Li; Licheng Zhou; Yuexi Chen; Xinyi Chen; Lanpeng Guo; Wenjian Zhang; Yufan Deng; Tiankun Li; Bingbing Chen; Hua-Yao Li; Huan Liu (Chemical Engineering Journal, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Morphological and physiological responses to aridity in narrowly- and widely-distributed plant species in drylands - Junlan Xiong; Weigang Hu; Allan Degen; Jie Peng; Longwei Dong; Li Yan; Qingqing Hou; Shuran Yao; Ying Sun; Xiaoting Wang; Yahui Zhang; Yan Deng; et al. (Science China Life Sciences, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

An energy-saving pH-asymmetric electrolyzer for simultaneous methane conversion and hydrogen production - Rong Chen; Furong Xie; Zinan Wu; Xiaoxin Li; Chao Deng; Zhenpeng Yao; Guo-Ming Weng (Science Bulletin, 2025)

Visualizing the bibliometrics of research trends and hotspots on grazing effects on global grassland vegetation - Qingqing Li; Zemin Ai; Xiaohu Dang; Huan Liu; Yong Cao; Mengjia Hou; Yuyan Yao; Yi Deng; Lie Xiao (Journal of Environmental Management, 2025)

Self-assembly of Zein-based nanoparticles for oral isoliquiritigenin delivery against Salmonella infections - Cang Li; Yu Huang; Yuchen Liu; Zhipeng Li; Yao Deng; Hao Ren; Donghao Zhao; Lu Han; Jian Sun (Innovative Food Science & Emerging Technologies, 2025)

A stable all-solid-state lithium metal battery achieved by optimizing the cathode-electrolyte interface through perovskite-coating-stabilized single crystal LiNi0.9Co0.05Mn0.05O2 cathode - Cheng Liu; Wenjin Li; Kaiyuan Deng; Puxi An; Rui Wang; Beisen Chen; Qingmei Xiao; Jiatao Wu; Lei Yao; Guangliang Gary Liu (Chemical Engineering Journal, 2025)

pH-sensitive nano-drug delivery systems dual-target endothelial cells and macrophages for enhanced treatment of atherosclerosis - Yiping Deng; Li Liu; Yao Li; Huan Ma; Chuang Li; Kexin Yan; Ji Tian; Chunhong Li (Drug Delivery and Translational Research, 2025)

Analysis of structural, functional properties and interaction mechanism of soy protein gel induced by high-performance microbial transglutaminase - Yu Deng; Ling Gao; Zehua Zhang; Zhengbing Guan; Nan Zheng; Pengling Wei; Shuang Du; Yao Wang; Zekun Li; Yongchao Cai; Xiaole Xia (Food Hydrocolloids, 2025)

A hydrogel-based composite facilitates efficient and recyclable tetracycline biodegradation in aquatic environments - Ze-Hua Cui; Qian He; Zhi-Peng Li; Yao Deng; Xiao-Ping Liao; Chaoqun Zhang; Jian Sun; Hao Ren; Lu Han (Environmental Research, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Water-in-eutectogel electrolytes for scalable solid-state electrochromic devices - Jianbo Deng; Mingjun Chen; Xiang Zhang; Hulin Zhang; Liping Hu; Shuokun Sun; Jiupeng Zhao; Yao Li (Chemical Engineering Journal, 2025)

Folic acid-targeted macrophage membrane-coated carbon quantum dot nanoplatform for dual drug and gene delivery in metastatic osteosarcoma therapy - Enyang Yao; Yang Li; Kai Deng; Wei He; Milad Ashrafizadeh; João Conde; Liyu Yang (Chemical Engineering Journal, 2025)

Staged pyrolysis of medical waste for high-value product generation: Impact of inter-component interactions on chlorine migration and light compounds formation - Yuhang Zheng; Tong Zhang; Aijun Li; Yongda Huang; Muhammad Usman; Chao Liao; Qian Deng; Hong Yao (Journal of Cleaner Production, 2025)

Hydroxyapatite combined with phosphate-solubilizing bacteria immobilized of Cd and inhibited the absorption of Cd by lettuce - Ke Wang; Junqing Zhang; Weilin Li; Zhongyan Deng; Randa S. Makar; Lunguang Yao; Hui Han (Journal of Environmental Chemical Engineering, 2025)

Dynamic Response of Rock Cut Slopes Under Train Loading: Insights from Uniaxial Wheel Load Tests and 3D Modeling - Weili Zhang; Qiang He; Li Deng; Cheng Qian; Qihai Yao (Geotechnical and Geological Engineering, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Slope unit-based comprehensive geohazard susceptibility assessment: SHAP interpretability and local InSAR deformation analysis - Peng Wang; Hongwei Deng; Jielin Li; Zhen Jiang; Guanglin Tian; Yao Liu (Advances in Space Research, 2025)

Baicalein inhibits Micropterus salmoides rhabdovirus replication in vitro and in vivo - Riying Deng; Shuangshuang Mao; Xiaoran Feng; Yuanyuan Li; Na Li; Lunguang Yao; Yinghui Qin (Aquaculture, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Synthesis of hollow HC-Ni0.96S@MXene/C nanobox as advanced anode for lithium-ion and sodium-ion battery - Song-Yi Liao; Jing Chen; Dao-Ren Deng; Cai-Yun Wu; Selina X. Yao; Yi Wang; Yu-Ming Ru; Xiao-Yan Li; Xu-Gang Shu; Yong-Gang Min (Chemical Engineering Journal, 2025)

Extracellular metabolites relieve the inhibitory effect of ferrous ions on microbial reduction of schwertmannite - Changdong Ke; Qian Yao; Yanping Deng; Siyu Zhang; Zhiliang Li; Renren Wu; Chuling Guo; Zhi Dang (Chemical Geology, 2025)

Dihydroartemisinin inhibits Micropterus salmoides rhabdovirus infection in vitro and in vivo - Yuanyuan Li; Peipei Zhang; Shuangshuang Mao; Xiaoran Feng; Haixiang Liu; Si Deng; Lunguang Yao; Yinghui Qin (Aquaculture, 2025)

Mechanisms controlling spatial variability of geogenic ammonium in coastal aquifers: Insights from Holocene sedimentary evolution - Yaojin Xiong; Yao Du; Jie Zhang; Yamin Deng; Xinwen Zhao; Qinghua Li; Yiqun Gan; Yanxin Wang (Water Research, 2025)

The near-complete genome assembly of pickling cucumber and its mutation library illuminate cucumber functional genomics and genetic improvement - Yao Tian; Kui Li; Tonghui Li; Wudi Gai; Jie Zhou; Xing Wang Deng; Yan Xue; Yun Deng; Hang He; Xingping Zhang (Molecular Plant, 2025)

Influence of phosphorus concentration on denitrifying glycogen accumulating organisms in endogenous partial denitrification system - Dong Li; Dongcai Deng; Mingrun Li; Yao Li; Zhengmao Dai; Wenqiang Wang; Jie Zhang (Journal of Environmental Chemical Engineering, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Controlled-release phosphate fertilizer improves soil fertility and soybean productivity by regulating soil microbial diversity and composition and increasing enzyme activities - Zhaoming Qu; Qi Chen; Hao Deng; Qin Wang; Shuihong Yao; Qianhui Chen; Hui Dong; Yanli Liu; Haojie Feng; Chengliang Li (Field Crops Research, 2025)

Synergies and trade-offs of crop diversification system for productive, energy budget, economic, and environmental indicators in Northeast China - Tao Sun; Haotian Chen; Li Yao; Xiaogang Yin; Zichao Zhao; Aixing Deng; Weijian Zhang; Xinhao Gao; Zhenwei Song (Field Crops Research, 2025)

Dry-processing of VN quantum dots/N, O, S-doped hierarchical porous carbon electrodes with high sulfur-loading for practical lithium-sulfur batteries - Shixian Chen; Gaohui Du; Yan Cheng; Di Han; Jiahao Deng; Yunting Wang; Huayu Li; Libing Yao; Dong Wang; Qingmei Su; Bingshe Xu (Chemical Engineering Journal, 2025)

Nature–based nutrient management through returning agricultural organic waste enhances soil aggregate organic carbon stability - Yini Wang; Yanzhong Yao; Bingbing Han; Simon Willcock; Jonathan Storkey; Xunzhuo Dong; Yunyao Zhong; Xiaozhong Wang; Yan Deng; Wei Zhang; Qirui Li; Xinping Chen; et al. (Agriculture, Ecosystems & Environment, 2025)

Advances and perspectives in biological control of postharvest fungal decay in citrus fruit utilizing yeast antagonists - Xiaojiao Li; Ou Chen; Wenjun Wang; Lili Deng; Shixiang Yao; Jian Ming; Hongyin Zhang; Kaifang Zeng (International Journal of Food Microbiology, 2025)

Corrosion behavior of WC-NiMoCrFeCo coating in seawater environment: Positive corrosion inhibition of a novel dynamic reaction product - Yu-Hang Zhang; Yao-Ning Sun; Xiu-Juan Fan; Bo-Kai Liao; Chun-Ming Deng; Shuang-Jian Li; Chao Wang; Yi-Fei Xv; Kang Li; Yi-Zhe Lv (Chemical Engineering Journal, 2025)

PbSQE3 and PbSQE6 regulates the formation of triterpenoid compounds in the russet mutant of ‘Dangshansuli variety’ pear - Zhenfeng Ye; Daozhi Yao; Qi Liu; Lingxia Chen; Lindong Dou; Jinhui Yu; Jie Deng; Zixiao Wu; Li Cao; Li Liu; Wei Heng (Acta Physiologiae Plantarum, 2025)

Spatiotemporal occurrence, distribution, and risk of steroid hormones along the coast of Guangdong, China - Xing Zhao; Yunlin Jiang; Hanqiang Deng; Yao Lu; Suimin Li; Yuxia Jiang; Kaifeng Sun (Frontiers in Marine Science, 2025)
Introduction Steroid hormones are widely present in the environment and pose potential risks to organisms. Previous studies of steroid hormones have predominantly focused on terrestrial environments, with few studies conducted in marine environments. Methods In this study, we analyzed the occurrence of 44 steroid hormones in seawater, sediment, and marine organisms collected from the coast of Guangdong, China. Results Total concentration of steroid hormones ranged from 0.11 to 30.15 ng/L in seawater, ND to 8.58 ng/g (dw) in sediments, and ND to 80.52 ng/g (ww) in organisms. The highest average concentrations of steroid hormones detected in seawater, sediments, and marine organisms were progestins, estrogens, and glucocorticoids, respectively. Steroid hormone concentrations in seawater were significantly higher during the dry season than the rainy season. The concentrations of steroid hormones in Guanghai Bay, the Pearl River Estuary, Daya Bay, and Zhelin Bay were significantly higher than those in other bays. Discussion Negative correlations were observed between steroid hormones and salinity, indicating a potential continental input. Risk assessment results indicated that 17α-ethinylestradiol in Zhelin Bay posed high risks. Nevertheless, the consumption of seafood does not pose a significant health risk to humans. To the best of our knowledge, this is the first study to concurrently analyze androgens, glucocorticoids, progestins, and estrogens in water, sediment, and organisms from diverse marine environments.

Sewage surveillance revealed the seasonality and prevalence of respiratory syncytial virus and its implications for seasonal immunization strategy in low and middle-income regions of China - Ziqiang Zhang; Qingxiang Li; Fenglan He; Zengguo Wang; Chulong Zhu; Junling Tu; Haifeng Li; Liu Yi; Yao Deng; Songzhe Fu (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Genome and transcriptome analysis of the lignite-degrading Trichoderma cf. simile WF8 strain highlights potential degradation mechanisms - Jinghua Yao; Yajuan Chen; Deyu Zhuo; Siqiao Chen; Baichao Xu; Congwei Yan; Wanrong Li; Hui Feng; Sheng Deng; Feng M. Cai; Andrei S. Steindorff; Irina S. Druzhinina; et al. (International Biodeterioration & Biodegradation, 2025)

Antibacterial mechanism of atmospheric cold plasma against Pseudomonas fluorescens and Pseudomonas putida and its preservation application on in-packaged red shrimp paste - Jiajie Hu; Yao Zhang; Weicong Pan; Qianyun Han; Yu Wei; Yuwei Li; Yi Hu; Xiaoguo Ying; Andrea Armani; Alessandra Guidi; Shanggui Deng (Food Chemistry, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Contrasting sources and fate of ammonium in groundwater systems of two large alluvial-lacustrine basins - Qinghua Li; Yaojin Xiong; Yamin Deng; Yiqun Gan; Yao Du (Applied Geochemistry, 2025)

Response of grassland greenhouse gas emissions to different human disturbances – A global Meta-analysis - Yong Cao; Zemin Ai; Xiaohu Dang; Huan Liu; Qingqing Li; Mengjia Hou; Yuyan Yao; Yi Deng; Lie Xiao; Shuaimeng Zhu (Agriculture, Ecosystems & Environment, 2025)

Seasonal Dynamics of Methane Fluxes from Groundwater to Lakes:Hydrological and Biogeochemical Controls - Hao Tian; Yao Du; Yamin Deng; Xiaoliang Sun; Shunjie Zhu; Jiawen Xu; Qinghua Li; Yiqun Gan; Yanxin Wang (Water Research, 2025)

Correlation analysis and modeling application from objective indicators to subjective evaluation of scented tea: A case study of rose tea - Ruolan Song; Meng Shen; Yanran Wang; Youyi Sun; Jiamu Ma; Qingyue Deng; Xueyang Ren; Xianxian Li; Yuan Zheng; Yingyu He; Feng Zhang; Mingxia Li; et al. (Food Chemistry, 2025)

Phthalate exposures, blood coagulation function, and assisted reproductive technology outcomes: Results from the TREE cohort study - Chong Liu; Chang-Jiang Liu; Wen-Qu Tian; Wen Yao; Yu Miao; Min Zhang; Xiao-Qiong Yuan; Yan-Ling Deng; Wen-Qing Lu; Yu-Feng Li; Qiang Zeng (Environmental Research, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

A novel method for rapidly simulating X-ray pulsar signals at a spacecraft - Lirong Shen; Yongshan Ba; Guang Sun; Xiaoping Li; Haifeng Sun; Zhongwen Deng; Shoubing Li; Dingkai Yao (Advances in Space Research, 2025)

Integrated impacts of mariculture on nitrogen cycling processes in the coastal groundwater of Beihai, southern China - Yuxi Bai; Yao Du; Yaojin Xiong; Yamin Deng; Yiqun Gan; Qinghua Li (Science of The Total Environment, 2024)

DEHP regulates ferritinophagy to promote testicular ferroptosis via suppressing SIRT1/PGC-1α pathway - Qi Zhu; Jianan Zhai; Zhengguo Chen; Zhifang Guo; Xiance Sun; Jing Li; Ningning Wang; Xiaofeng Yao; Cong Zhang; Haoyuan Deng; Shaopeng Wang; Guang Yang (Science of The Total Environment, 2024)

Numerical modeling of graded sediment transport with limited bed material supply – A case study in the Middle Yangtze River - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng; Jie Li; Yao Xiao (Journal of Hydrology, 2024)

High-resolution full-coverage ozone (O3) estimates using a data-driven spatial random forest model in Beijing-Tianjin-Hebei region, China - Junyu Wang; Jian Qian; Jiayi Chen; Sheng Li; Menghan Yao; Qianqian Du; Na Yang; Tao Zhang; Fei Yin; Ying Deng; Jing Zeng; Chenglin Tao; et al. (Journal of Hazardous Materials, 2024)

Accurate and stable detection of p-phenylenediamine antioxidants and their transformation products in aquatic products using antioxidant protection – Analysis of actual aquatic products - Qicai Zhang; Xianli Wang; Chengbin Liu; Huaxi Li; Zhongsheng Deng; Chunxia Yao; Yameng Li; Qinxiong Rao; Weiguo Song (Journal of Hazardous Materials, 2024)

Differential analysis of sorting nexin 10 and sterol regulatory element–binding protein 2 expression in inflammatory bowel disease - Bicheng Xie; Anxing Zhang; Canmei Li; Yu Liu; Yao Deng; Ruochang Li; Haichun Qin; Bian Wu; Tian He; Danfeng Lan (Immunologic Research, 2024)

Separation and spatial variations of typhoon and non‐typhoon rainfall at different timescales in typical region of southeast China - Senzhen Wang; Xingwei Chen; Huaxia Yao; Weifang Ruan; Zipeng Gu; Xiaocheng Li; Ying Chen; Meibing Liu; Haijun Deng (International Journal of Climatology, 2024)
Rainfall in East Asia is affected by two rain‐bearing systems: tropical cyclones and monsoon‐related frontal systems. Distinguishing typhoon rainfall (TR) and non‐typhoon rainfall (non‐TR) helps to understand the evolution process of regional rainfall at different timescales. Taking Fujian Province in the southeast coast of China as an example, based on the fixed box approach of separating TR, the method of determining the size of fixed box is explored. TR and non‐TR are separated in Fujian Province, and the spatial variations of TR and non‐TR at different timescales (annual, monthly, day of annual‐maximum‐rain) are analysed. The results showed that (1) according to the relationship between the sizes of fixed box and the rate of change of TR, the size of fixed box could be reasonably determined; thus, the expended size of fixed box suitable for separating TR in Fujian was 3.5°, namely the range of 20°–31.8°N and 112.3°–124.2°E. (2) The spatial variations of TR at different timescales in Fujian were similar: TR decreased from the coast to the inland, and the northeast coast of Fujian was the high‐value region. Due to the difference of water vapour sources, non‐TR in March–June increased from the coast to the inland, but the high value of non‐TR in July–September was distributed in the eastern coast. (3) The contribution rates of average TR to the total rainfall of the year, July–September and 1 day were 12.8%, 34.6% and 35.7%, respectively. In eastern coast, TR in July–September accounted for 1/3–1/2 of total rainfall, and the rainfall in a day was mainly affected by TR; while in western inland, rainfall was mainly non‐TR and the influence of TR was less than 1/4.

Ruminant livestock TR V(D)J genes and CDR3 repertoire - Fengli Wu; Yunlan Deng; Xinsheng Yao; Jun Li (Veterinary Immunology and Immunopathology, 2024)

WITHDRAWN: Is antioxidant activity of flavonoids mainly through the hydrogen-atom transfer mechanism? - Xuan Chen; Zeyuan Deng; Chengyue Zhang; Shilian Zheng; Yao Pan; Hongming Wang; Hongyan Li (Food Research International, 2024)

Effects of photodegradation on the composition characteristics and metal binding behavior of sediment-derived dissolved organic matter (SDOM) in nansi lake, China - Zhaoli Sun; Xin Yao; Dongling Sang; Shanshan Wang; Weiwei Lü; Xiao Sun; YingHao Zhang; Huanguang Deng; Tingting Li (Environmental Research, 2024)

Dielectric screening modulating charge carrier recombination in high-performance of CsPbI2Br carbon-based perovskite solar cells - Fengli Liu; Yuan Xu; Ruoshui Li; Chunyan Deng; Lin Gao; Haozhen Deng; Yu Jing; Dongbin Jiang; Qing Yao; Chenfang Zhong; Deng Wang; Jihuai Wu; et al. (Chemical Engineering Journal, 2024)

Modulating polarization and conduction loss for optimized electromagnetic wave absorption performance of FeNi/ZnO/C/Ni3ZnC0.7 composites - Fangyu Gan; Zhenpeng Li; Qingrong Yao; Shasha Jiang; Xiaochang Yu; Jianqiu Deng; Zhao Lu; Lichun Cheng; Maomi Zhao; Huaiying Zhou (Chemical Engineering Journal, 2024)

3D printed microplasma optical emission spectrometry coupled with ZIF-8 based dispersive solid-phase extraction for field analysis of waterborne arsenic - Jiahui Yang; Yao Lin; Xi Wang; Yuanyuan Li; Yurong Deng; Chengbin Zheng (Analytica Chimica Acta, 2024)

RustQNet: Multimodal deep learning for quantitative inversion of wheat stripe rust disease index - Jie Deng; Danfeng Hong; Chenyu Li; Jing Yao; Ziqian Yang; Zhijian Zhang; Jocelyn Chanussot (Computers and Electronics in Agriculture, 2024)

Tas2R143 regulates the expression of the Blood-Testis Barrier tight junction protein in TM4 cells through the NF-κB signaling pathway - Xue Wang; Jin dan Wang; Xin Li; Tianrun Wang; Jiaqi Yao; Ruxue Deng; Wenchang Ma; Shengjun Liu; Zhanbo Zhu (Theriogenology, 2024)

Comparison with Polygonatum cyrtonema Hua steaming with huangjiu or honey based on UPLC-Q-Exactive MS/MS analysis combined with multi-component variation - Zeyuan Deng; Xiangjie Yao; Chunxiao Li; Bing Zhang; Ruimin Zhong; Hongyan Li (Food Bioscience, 2024)

The influence mechanism of fulvic acid on Fe(II)-catalyzed transformation of Cr(III)-bearing schwertmannite: pH effect and nanoscale redistribution of Cr and C - Qian Yao; Limiao Cai; Xiaohu Jin; Xiaofei Li; Changdong Ke; Yirong Deng; Chuling Guo; Guining Lu; Zhi Dang; Xiaoyun Yi (Chemical Engineering Journal, 2024)

Preparation and applications of Hydrogen-Bonded organic framework membranes - Wei-Hua Deng; Xue Wang; Ke Xiao; Yunbin Li; Chulong Liu; Zizhu Yao; Lihua Wang; Zhibin Cheng; Yuanchao Lv; Shengchang Xiang; Zhangjing Zhang (Chemical Engineering Journal, 2024)

Central role of Sigma-1 receptor in ochratoxin A-induced ferroptosis - Wenying Chen; Lingyun Han; Ruiran Yang; Hongwei Wang; Song Yao; Huiqiong Deng; Shuangchao Liu; Yao Zhou; Xiao Li Shen (Archives of Toxicology, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Shelf life extended: Focus on microbiota identification, nutrition value, color difference and lipid oxidation of puffed bean products - Huanhuan Wang; Zeyuan Deng; Bing Zhang; Chunfeng Ouyang; Shuang Liu; Yao Pan; Hongyan Li (Food Control, 2024)

FAP expression dynamics and role in silicosis: Insights from epidemiological and experimental models - Xuedan Deng; Zhiwei Cheng; Yiping Li; Meixiu Duan; Jingyi Qi; Changfu Hao; Wu Yao (Environmental Pollution, 2024)

Relating the carbon sources to denitrifying community in full-scale wastewater treatment plants - Jinling Chen; Xia Tang; Xuewei Wu; Biping Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Xuhan Deng; Xiaojing Xie; Chaohai Wei; et al. (Chemosphere, 2024)

Curcumin inhibits PAT-induced renal ferroptosis via the p62/Keap1/Nrf2 signalling pathway - Jianan Zhai; Zhengguo Chen; Qi zhu; Zhifang Guo; Xiance Sun; Liping Jiang; Jing Li; Ningning Wang; Xiaofeng Yao; Cong Zhang; Haoyuan Deng; Shaopeng Wang; et al. (Toxicology, 2024)

Asymmetric capacitive deionization based on pore structures of biochar - Yuqi Li; Changlin Wang; Dengfei Deng; Yixuan Qiao; Guangyuan Yao; Yang Wang (Desalination, 2024)

Source-oriented health risk assessment of groundwater nitrate by using EMMTE coupled with HHRA model - Huanhuan Shi; Yao Du; Yaojin Xiong; Yamin Deng; Qinghua Li (Science of The Total Environment, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

The improvement of tyrosol bioavailability by encapsulation into liposomes using pH-driven method - Yexuan Yao; Li Ma; Chengwei Yu; Ce Cheng; Hongxia Gao; Teng Wei; Litong Li; Zhiyue Wang; Wei Liu; Zeyuan Deng; Liqiang Zou; Ting Luo (Food Chemistry, 2024)

Polymethoxyflavones from citrus peel: advances in extraction methods, biological properties, and potential applications - Qiong Peng; Yao Zhang; Mingxuan Zhu; Feng Bao; Jing Deng; Wen Li (Critical Reviews in Food Science and Nutrition, 2024)

Underlying mechanisms governing on distribution and stratification of DOM during seasonal freeze-thaw cycles - Weiying Feng; Yuxin Deng; Fang Yang; Tingting Li; Fu Wang; Qi Zhang; Haipeng Yao; Haiqing Liao (Science of The Total Environment, 2024)

Exposure to the environmental pollutant chlorpyrifos induces hepatic toxicity through activation of the JAK/STAT and MAPK pathways - Huiyang Fu; Yao Ge; Xiyuan Liu; Siwei Deng; Jun Li; Peng Tan; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Effects of different reclamation measures on soil quality restoration in open-pit mines: A meta-analysis based on the Chinese Loess Plateau - Yong Cao; Zemin Ai; Xiaohu Dang; Mengjia Hou; Huan Liu; Qingqing Li; Yuyan Yao; Yi Deng; Shuaimeng Zhu; Lie Xiao (Ecological Engineering, 2024)

Facile construction of multifunctional 3D smart MOF-based polyurethane sponges with photocatalytic ability for efficient separation of oil-in-water emulsions and co-existing organic pollutant - Qidong Zha; Yuankun Yao; Zuozhu Yin; Yuanting Deng; Zihao Li; Yu Xie; Yuhua Chen; Chenggang Yang; Yidan Luo; Mingshan Xue (Chemical Engineering Journal, 2024)

An effective cross-scenario remote heart rate estimation network based on global–local information and video transformer - Guoliang Xiang; Song Yao; Yong Peng; Hanwen Deng; Xianhui Wu; Kui Wang; Yingli Li; Fan Wu (Physical and Engineering Sciences in Medicine, 2024)

Paleontology Knowledge Graph for Data-Driven Discovery - Yiying Deng; Sicun Song; Junxuan Fan; Mao Luo; Le Yao; Shaochun Dong; Yukun Shi; Linna Zhang; Yue Wang; Haipeng Xu; Huiqing Xu; Yingying Zhao; et al. (Journal of Earth Science, 2024)

Molecular characterization of a single-negative-stranded RNA virus from the rice blast fungus Magnaporthe oryzae isolate NJ39 - Hang Ding; Yao Wang; Cong Li; Simin Shuai; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Archives of Virology, 2024)

An Asp376Glu substitution and P450s-involved metabolism endow resistance to ALS inhibitors in an Ammannia auriculata Willd. Population - Wei Deng; Sai Yao; Yang Li; Hanqi Yin; Qian Yang; Shuzhong Yuan (Pesticide Biochemistry and Physiology, 2024)

Cadmium biosorption and mechanism investigation using two cadmium-tolerant microorganisms isolated from rhizosphere soil of rice - Zu-xuan Yan; Yi Li; Shuai-ying Peng; Lei Wei; Bao Zhang; Xin-yao Deng; Min Zhong; Xin Cheng (Journal of Hazardous Materials, 2024)

Determination of high-risk factors and related spatially influencing variables of heavy metals in groundwater - Huanhuan Shi; Yao Du; Yueping Li; Yamin Deng; Yanqiu Tao; Teng Ma (Journal of Environmental Management, 2024)

Interface effect of Fe doped NiSe/Ni3Se2 heterojunction as highly efficient electrocatalysts for overall water splitting - Ruxin Deng; Huiqin Yao; Yixuan Wang; Chaonan Wang; Siqi Zhang; Shaoshi Guo; Yongliang Li; Shulan Ma (Chemical Engineering Journal, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Simultaneous removal of As(V) and sulfamethazine from water in FeS2-H2O2 system - Wen Li; Shanshan Yang; Shuiyu Sun; Tianming Wang; Qi Yao; Jingyi Zhan; Shanwen Ye; Yating Liang; Yunzhuo Deng; Wenxiang Wang; Hongsheng Fang; Yunmei Cai (Chemical Engineering Journal, 2024)

Estimating the mutually adjusted health effects of short- and long-term exposure to PM2.5 on respiratory mortality in a population-based study - Yi Zhang; Jing Zeng; Xinyue Tian; Siwei Zhai; Jingfei Huang; Xuelin Li; Sheng Li; Junyu Wang; Menghan Yao; Qianqian Du; Wei Wang; Tao Zhang; et al. (Atmospheric Pollution Research, 2024)

Characterization of whole genomes from recently emerging Mpox cases in several regions of China, 2023 - Changcheng Wu; Lunbiao Cui; Yang Pan; Ziquan Lv; Mingxiao Yao; Wenling Wang; Fei Ye; Weibang Huo; Li Zhao; Baoying Huang; Fengcai Zhu; Roujian Lu; et al. (Science China Life Sciences, 2024)

IRE1α: from the function to the potential therapeutic target in atherosclerosis - Zheng-Yang Zhou; Li Wu; Yi-Fan Liu; Mu-Yao Tang; Jing-Yi Tang; Ya-Qian Deng; Lei Liu; Bin-Bin Nie; Zi-Kai Zou; Liang Huang (Molecular and Cellular Biochemistry, 2024)

Mixed plantations with N-fixing tree species maintain ecosystem C:N:P stoichiometry: Implication for sustainable production - Xianyu Yao; Dafeng Hui; Shuo Xing; Qianchun Zhang; Jingwen Chen; Zihua Li; Yang Xu; Qi Deng (Soil Biology and Biochemistry, 2024)

Citrus transcription factor CsERF098 cooperates with CsWRKY70 to participate in response of fruit to green mold - Ting Li; Wenjun Wang; Qi Chen; Ou Chen; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Numerical simulation analysis of debris filtration in the bottom nozzle - Shuang Deng; Quan-yao Ren; Jing Zhang; Xin Duan; Fa-wen Zhu; Yong Xin; Xin-Yu Yang; Quan Li; Ying-wei Wu (Annals of Nuclear Energy, 2024)

The regulation of AMPK pathway in liver abnormal lipid deposition caused by high carbohydrate diet in rice field eel - Yao Deng; Jiamin Li; Shanshan Wu; Peng Fang; Wei Lei; Huanhuan Huo; Mo Peng (Animal Feed Science and Technology, 2024)

Xiashengella succiniciproducens gen. nov., sp. nov., a succinate-producing bacterium isolated from an anaerobic digestion tank in the family Marinilabiliaceae of the order Bacteroidales - Hao-Jie Huang; Xi Zhang; Xin-Wei Sun; Biao Chen; Xiu-Tong Li; Nan Zhou; Rashidin Abdugheni; Qiu-Yin Cheng; Tie-Jun Zhang; Yao Liu; Yong Jiang; Ye Deng; et al. (Archives of Microbiology, 2024)

Death-associated protein 3 in cell death and beyond - Ting Cao; Xuling Luo; Binjiao Zheng; Yao Deng; Yu Zhang; Yuyan Li; Wenwen Xi; Meng Guo; Xuefeng Yang; Zhiyue Li; Bin Lu (Genome Instability & Disease, 2024)

Dietary tributyrin supplementation promotes the growth by improving intestinal digestive and antioxidant capacity and the abundance of intestinal beneficial bacteria for swimming crab (Portunus trituberculatus) - Hongyu Peng; Min Jin; Tingting Zhu; Shichao Xie; Wenhao Zhan; Yao Deng; Yuhang Yang; Yuhui Cui; Xiangkai Li; Qicun Zhou (Aquaculture, 2024)

Mediation of the JNC/ILC2 pathway in DBP-exacerbated allergic asthma: A molecular toxicological study on neuroimmune positive feedback mechanism - Xiaomin Xie; Yan Li; Biao Yan; Qi Peng; Runming Yao; Qihong Deng; Jinquan Li; Yang Wu; Shaohui Chen; Xu Yang; Ping Ma (Journal of Hazardous Materials, 2024)

Composition characteristics and metal binding behavior of macrophyte-derived DOM (MDOM) under microbial combined photodegradation: A state closer to actual macrophytic lakes - Tuantuan Fan; Xin Yao; Dongling Sang; Li Liu; Zhaoli Sun; Huanguang Deng; Yinghao Zhang; Xiao Sun (Journal of Hazardous Materials, 2024)

Effect of melatonin on cryopreservation of Beijing you chicken (gallus gallus) spermatozoa - Laiqing Yan; Junying Li; Guangdong Li; Wenkui Ma; Yunjie Liu; Xuening Liu; Mengmeng Zhao; Pengyun Ji; Yao fu; Qihao Zheng; Xuemei Deng; Guoshi Liu (Cryobiology, 2024)

Emission characteristics of carbonyl compounds from open burning of typical subtropical biomass in South China - Chunlin Zhang; Yiting Cai; Qian Yao; Xiaoting Liu; Lin Song; Jiangyong Li; Shuo Deng; Hao Wang; Boguang Wang (Chemosphere, 2024)

Characteristics of dissolved organic matter contribute to Geogenic ammonium enrichment in coastal versus alluvial-lacustrine aquifers - Yaojin Xiong; Yao Du; Zhaohui Liu; Yamin Deng; Teng Ma; Qinghua Li; Yanxin Wang (Water Research, 2024)

α−FeOOH@HTC with abundant oxygen vacancy enhances the adsorption of As(III) in different phosphate environments - Huidi Zhang; Junhui Yang; Yao Deng; Yanmei Li; Jing Wang; Lin Wang; Wenlei Wang (Journal of Environmental Chemical Engineering, 2024)

Hydrothermal synthesis of lepidocrocite-like potassium lithium titanate K0.80Li0.267Ti1.733O4 (KLTO) with superior polarization performance - Kai Huo; Jinyang Zhao; Junze Zhuang; Zhenhua Yao; Maocong Hu; Baoxiang Wang; Guicun Li; Kangqing Deng; Xuguang Liu (Chemical Engineering Journal, 2024)

Study on the trade-off/synergy between ecosystem services and human well-being based on land use in Weinan City, China - Zemin Ai; Yuyan Yao; Xiaohu Dang; Xinghua Li; Mengjia Hou; Yi Deng; Lie Xiao; Ting Li; Tao Wang (Environmental Science and Pollution Research, 2024)

Assessing biogeochemical controls on porewater dissolved inorganic carbon cycling in the gas hydrate-bearing sediments of the Makran accretionary wedge, Northeastern Arabian Sea off Pakistan - Yuanqing Chen; Sinan Xu; Weining Liu; Zhen Zhang; Tianbang Yang; Xiao Xiao; Xiguang Deng; Jiangtao Li; Huiqiang Yao; Zijun Wu (Frontiers in Marine Science, 2024)
Quantitatively assessing the porewater dissolved inorganic carbon (DIC) cycling in methane-enriched marine sediments is crucial to understanding the contributions of different carbon sources to the global marine carbon pool. In this study, Makran accretionary wedge was divided into Zone 1 (high methane flux area) and Zone 2 (background area). Porewater geochemical compositions (Cl – , SO 4 2– , NH 4 + , Mg 2+ , Ca 2+ , Ba 2+ , DIC and δ 13 C-DIC) and a reaction-transport model were used to determine the DIC source and calculate the DIC flux through carbonate precipitation and releasing into overlying seawater in sediments. Zone 1 is characterized by the shallower depth of sulfate-methane transition (SMT), where most of porewater sulfate was consumed by anaerobic oxidation of methane (AOM). In contrast, a relatively low flux of methane diffusion in Zone 2 results in a deeper SMT depth and shallow sulfate is predominantly consumed by organoclastic sulfate reduction (OSR). Based on the porewater geochemical profiles and δ 13 C mass balance, the proportions of porewater DIC originating from methane were calculated as 51% in Zone 1 and nearly 0% in Zone 2. An increase of porewater DIC concentration leads to authigenic carbonate precipitation. Solid total inorganic carbon (TIC), X-ray diffractometry (XRD) and scanning electron microscopy (SEM) analysis display that carbonate content increases with depth and aragonite appears at or below the depths of SMT. Meanwhile, the flux of DIC released from sediments calculated by the reaction-transport model is 51.3 ~ 90.4 mmol/m 2 ·yr in Zone 1, which is significantly higher than that in Zone 2 (22.4 mmol/m 2 ·yr). This study demonstrates that AOM serves as the dominant biogeochemical process regulating the porewater DIC cycle, which has an important impact on the authigenic carbonate burial and the seawater carbonate chemistry.

pH-responsive bentonite nanoclay carriers control the release of benzothiazolinone to restrain bacterial wilt disease - Liang Yang; Yao Wang; Yijia Liang; Haibin Deng; Jun Wang; Yuhao Dai; Fuyou Guo; Hong Zhou; Shili Li; Wei Ding (Pesticide Biochemistry and Physiology, 2024)

V-ATPase E mediates Cry2Ab binding and toxicity in Helicoverpa armigera - Yuge Zhao; Pin Li; Xue Yao; Yuepu Li; Yu Tian; Guiying Xie; Zhongyuan Deng; Shuxia Xu; Jizhen Wei; Xianchun Li; Shiheng An (Pesticide Biochemistry and Physiology, 2024)

Afforestation increased the microbial necromass carbon accumulation in deep soil on the Loess Plateau - Yao Li; Baorong Wang; Yuhan Zhang; Deng Ao; Chenglong Feng; Pan Wang; Xuejuan Bai; Shaoshan An (Journal of Environmental Management, 2024)

The designation of intrinsic flame-retarding vinyl ester resins with high mechanical property, optical transparency and degradability - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang; De-Yi Wang (Chemical Engineering Journal, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Soil acidification suppresses phosphorus supply through enhancing organomineral association - Yuanliu Hu; Ji Chen; Dafeng Hui; Jianling Li; Xianyu Yao; Deqiang Zhang; Qi Deng (Science of The Total Environment, 2023)

Current status of cyhalofop-butyl and metamifop resistance and diversity of the ACCase gene mutations in Chinese sprangletop (Leptochloa chinensis) from China - Wei Deng; Yang Li; Sai Yao; Jiawen Wu; Axiu Zhu; Qian Yang; Shuzhong Yuan (Pesticide Biochemistry and Physiology, 2023)

Association of selenium profile with neutralizing antibody response to inactivated SARS-CoV-2 vaccination - Sikang Gao; Na Ren; Taoping Sun; Qi Nie; Sitian Liu; Xuyang Geng; Yao Deng; Zefang Lin; Yu Liu; Li Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

The regulation of biochar surface potential to achieve rapid capacitive deionization - Changlin Wang; Yuqi Li; Yixuan Qiao; Nyan Lynn Tut; Dingfei Deng; Qianfeng Pan; Guangyuan Yao; Yang Wang (Journal of Environmental Chemical Engineering, 2023)

Machine learning-based monosaccharide profiling for tissue-specific classification of Wolfiporia extensa samples - Shih-Yi Hsiung; Shun-Xin Deng; Jing Li; Sheng-Yao Huang; Chen-Kun Liaw; Su-Yun Huang; Ching-Chiung Wang; Yves S.Y. Hsieh (Carbohydrate Polymers, 2023)

Effect of depositional evolution on phosphorus enrichment in aquifer sediments of alluvial-lacustrine plain - Meihui Liu; Yao Du; Yamin Deng; Yueping Li; Yanqiu Tao; Yiqun Gan; Teng Ma (Science of The Total Environment, 2023)

RETRACTED: Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2023)

Vertical leaching of paleo-saltwater in a coastal aquifer–aquitard system of the Pearl River Delta - Shengchao Yu; Jiu Jimmy Jiao; Xin Luo; Hailong Li; Xuejing Wang; Qianqian Wang; Meng Yao; Yifan Guo; Zhiyun Deng; Jinchao Zuo (Journal of Hydrology, 2023)

The role of high humidity on extreme-temperature-related mortality in central China - Peizhi Deng; Yan Li; Shenxin Li; Yuxin Feng; Donghui Jin; Yiping Yang; Yang Xie; Yao Lu; Qiuping Zhao; Hong Yuan (Air Quality, Atmosphere & Health, 2023)

A new sesquiterpenoid from the aconitum -derived fungus Aspergillus fumigatus M1 - Hao Ding; Jia-Peng Wang; Si-Ping Deng; Jun-Li Gan; Bing-Xian Li; Ling-Ling Yao; Sheng-Qi Zhang; Le Cai; Zhong-Tao Ding (Natural Product Research, 2023)

Modeling and optimization of Graphene Oxide (GO) membranes for nanofiltration with artificial neural networks - Haodong Yang; Zhe Chen; Yong Li; Lei Yao; Geming Wang; Quanrong Deng; Ping Fu; Shenggao Wang (Journal of Water Process Engineering, 2023)

Reactive migration mechanism of Fe2+ and As3+ during groundwater discharge into river water: Insight from sand column experiments - Xiyu Deng; Yao Huang; Ziwei Guo; Shengjun Mao; Shuang Li; Lei Tong; Minjing Li; Hui Liu (Journal of Hydrology, 2023)

Developing robust organic afterglow emulsion for dissolved oxygen sensing - Ju Huang; Xinjian Deng; Jiuyang Li; Guangming Wang; Xun Li; Honghong Yao; Chuanhu Lei; Kaka Zhang (Chemical Engineering Journal, 2023)

Description of Xanthocytophaga agilis sp. nov. and Xanthocytophaga flavus sp. nov. of the new genus Xanthocytophaga gen. nov and the proposal of Rhodocytophagaceae fam. nov. within the order Cytophagales - Xianjiao Zhang; Guang-Da Feng; Yang Liu; Fan Yang; Yanxuan Li; Xiaoqin Deng; Honghui Zhu; Qing Yao (Archives of Microbiology, 2023)

Targeted preparation of biochar for the application as composting additive: Influence mechanism of feedstock properties on biochar derived from traditional Chinese herb residue - Haoyu Tang; Aijun Li; Linlin Yi; Yongda Huang; Qian Deng; Yangwei Wu; Hong Yao (Process Safety and Environmental Protection, 2023)

Structure and anti-inflammatory activity of neo-clerodane diterpenoids from Scutellaria barbata - ShuTing Li; Dan Xu; Jing Jia; Wenbo Zou; JieYing Liu; Yao Wang; Kun Zhang; Xi Zheng; Yan-Yan Ma; Xuejian Zhang; Deng-Gao Zhao (Phytochemistry, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Temperature‐mediated microbial carbon utilization in China's lakes - Yao Guo; Songsong Gu; Kaixuan Wu; Andrew J. Tanentzap; Junqi Yu; Xiangfen Liu; Qianzheng Li; Peng He; Dongru Qiu; Ye Deng; Pei Wang; Zhenbin Wu; et al. (Global Change Biology, 2023)
Microbes play an important role in aquatic carbon cycling but we have a limited understanding of their functional responses to changes in temperature across large geographic areas. Here, we explored how microbial communities utilized different carbon substrates and the underlying ecological mechanisms along a space‐for‐time substitution temperature gradient of future climate change. The gradient included 47 lakes from five major lake regions in China spanning a difference of nearly 15°C in mean annual temperatures (MAT). Our results indicated that lakes from warmer regions generally had lower values of variables related to carbon concentrations and greater carbon utilization than those from colder regions. The greater utilization of carbon substrates under higher temperatures could be attributed to changes in bacterial community composition, with a greater abundance of Cyanobacteria and Actinobacteriota and less Proteobacteria in warmer lake regions. We also found that the core species in microbial networks changed with increasing temperature, from Hydrogenophaga and Rhodobacteraceae, which inhibited the utilization of amino acids and carbohydrates, to the CL500‐29‐marine‐group , which promoted the utilization of all almost carbon substrates. Overall, our findings suggest that temperature can mediate aquatic carbon utilization by changing the interactions between bacteria and individual carbon substrates, and the discovery of core species that affect carbon utilization provides insight into potential carbon sequestration within inland water bodies under future climate warming.

Prediction of pyrolysis product yield of medical waste based on BP neural network - Yangwei Wu; Aijun Li; Su Lei; Tong Zhang; Qian Deng; Haoyu Tang; Hong Yao (Process Safety and Environmental Protection, 2023)

ACCase gene mutations and P450-mediated metabolism contribute to cyhalofop-butyl resistance in Eleusine indica biotypes from direct-seeding paddy fields - Wei Deng; Yang Li; Sai Yao; Zhiwen Duan; Qian Yang; Shuzhong Yuan (Pesticide Biochemistry and Physiology, 2023)

Research on migration and transformation behavior of selenium during the dual-alkali wet flue gas deacidification process in the simulated flue gas - Huasheng Wang; Bing Yuan; Hongyun Hu; Lu Dong; Chan Zou; Guangzhao Guo; Shuang Deng; Songgeng Li; Hong Yao (Fuel, 2023)

Disease specific air quality health index (AQHI) for spatiotemporal health risk assessment of multi-air pollutants - Xun Deng; Bin Zou; Shenxin Li; Jian Wu; Chenjiao Yao; Minxue Shen; Jun Chen; Sha Li (Environmental Research, 2023)

Wnt/β-Catenin Promotes the Osteoblastic Potential of BMP9 Through Down-Regulating Cyp26b1 in Mesenchymal Stem Cells - Xin-Tong Yao; Pei-pei Li; Jiang Liu; Yuan-Yuan Yang; Zhen-Ling Luo; Hai-Tao Jiang; Wen-Ge He; Hong-Hong Luo; Yi-Xuan Deng; Bai-Cheng He (Tissue Engineering and Regenerative Medicine, 2023)

The fertilization process in Lithocarpus dealbatus (Fagaceae) and its implication on the sexual reproduction evolution of Fagales - Kaiping Yao; Min Deng; Lin Lin; Jinjin Hu; Xiaorui Yang; Qiansheng Li; Zhuo Feng (Planta, 2023)

Parametric analysis and multi-objective optimization of the coupling beam pile structure foundation - Yousheng Deng; Keqin Zhang; Zhigang Yao; Huiling Zhao; Long Li (Ocean Engineering, 2023)

Comparative study of the combustion and kinetic characteristics of fresh and naturally aged pine wood - Jun Deng; Tong-shuang Liu; Min Yao; Xin Yi; Guang-Xing Bai; Qian-rui Huang; Zheng Li (Fuel, 2023)

Association of long-term ambient fine particulate matter (PM2.5) and incident non-alcoholic fatty liver disease in Chinese adults - Peizhi Deng; Haibo Tang; Liyong Zhu; Jingwen Duan; Fei Li; Yalan Li; Jie Wang; Jingjing Wu; Changjiang Meng; Wei Wang; Yiping Yang; Zhiheng Chen; et al. (Environmental Pollution, 2023)

Coupled effects of sedimentary iron oxides and organic matter on geogenic phosphorus mobilization in alluvial-lacustrine aquifers - Xinxin Zhang; Xianzhong Ke; Yao Du; Yanqiu Tao; Jiangkai Xue; Qinghua Li; Xianjun Xie; Yamin Deng (Science of The Total Environment, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Iron [Fe(0)]-carbon micro-electrolysis enhances simultaneous nitrogen and phosphorus removal in vertical flow constructed wetlands for advanced treatment of reclaimed water - Zhifeng Hu; Hong Yao; Shihai Deng; Chao Zhang; Shuai Peng; Zhongguo Zhang; Desheng Li (Journal of Environmental Management, 2023)

Excessive ER-phagy contributes to ochratoxin A-induced apoptosis - Huiqiong Deng; Wenying Chen; Boyang Zhang; Yiwen Zhang; Lingyun Han; Qipeng Zhang; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

A high-throughput atomic emission analyzer for simultaneous field detection of dissolved inorganic and organic carbon in seawater and lake water - Yubin Su; Yao Lin; Yuanyuan Li; Tian Ren; Yurong Deng; Chengbin Zheng (Analytica Chimica Acta, 2023)

The root-associated Fusarium isolated based on fungal community analysis improves phytoremediation efficiency of Ricinus communis L. in multi metal-contaminated soils - Huaxiong Yao; Wenguang Shi; Xing Wang; Junyan Li; Meiqi Chen; Jianbin Li; Danting Chen; Lin Zhou; Zujun Deng (Chemosphere, 2023)

Enrichment of geogenic phosphorus in a coastal groundwater system: New insights from dissolved organic matter characterization - Zhaohui Liu; Yao Du; Yamin Deng; Yanwen Huang; Xinwen Zhao; Qinghua Li (Chemosphere, 2023)

Modification mechanism of protein in rice adjuncts upon extrusion and its effects on nitrogen conversion during mashing - Lijun Jiang; Jialin Song; Mingming Qi; Wenjing Suo; Yuxin Deng; Yao Liu; Luxia Li; Dongliang Zhang; Chenjie Wang; Hongjun Li (Food Chemistry, 2023)

A facile construction of bifunctional core–shell–shell structured magnetic metal–organic frameworks for detection and removal of tetracycline - Jin Li; Ruihong Yao; Bowen Deng; Zhijian Li; Kai Tuo; Congbin Fan; Gang Liu; Shouzhi Pu (Chemical Engineering Journal, 2023)

Strength and Failure Mode of Expansive Slurry-Inclined Layered Rock Mass Composite Based on Mohr–Coulomb Criterion - Nan Yao; Xingmin Deng; Binyu Luo; Felix Oppong; Pengcheng Li (Rock Mechanics and Rock Engineering, 2023)

Characterization of phytopathogen-preying Hyalangium versicolor sp. nov., and proposal for the reclassification of Cystobacter gracilis as Hyalangium gracile comb. Nov - Xianjiao Zhang; Guangda Feng; Yang Liu; Jiali Li; Xiaoqin Deng; Qing Yao; Honghui Zhu (Archives of Microbiology, 2023)

Transcription factor CsERF1B regulates postharvest citrus fruit resistance to Penicillium digitatum - Ting Li; Wenjun Wang; Qi Chen; Jialin Chen; Xuan Zhang; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Effect of lithofacies on differential movable fluid behaviors of saline lacustrine fine-grained mixed sedimentary sequences in the Jimusar sag, Junggar Basin, NW China: Forcing mechanisms and multi-scale models - Wei Yang; Yaohua Wang; Ming Xie; Yingyan Li; Yang Gao; Yuan Deng; Changfu Xu; Jianhua Qin; Shouchang Peng; Leilei Yang; Linjie Yao; Haodong Hou (Marine and Petroleum Geology, 2023)

Depression of electro-oxidation of Ti3C2Tx MXene Joule heater by alternating current for Joule heating membrane distillation - Ziquan Wang; Zheng Li; Bo Yong; Haiyan Huang; Lei Yao; Libo Deng (Chemical Engineering Journal, 2023)

Oxidation of simulated wastewater by Fe2+-catalyzed system: The selective reactivity of chlorine radicals and the oxidation pathway of aromatic amines - Xiaojun Lai; Nuoyi Huang; Xiaohua Zhao; Yang Li; Yao He; Jiesen Li; Jinhuan Deng; Xun-an Ning (Chemosphere, 2023)

Properties and metal binding behaviors of sediment dissolved organic matter (SDOM) in lakes with different trophic states along the Yangtze River Basin: A comparison and summary - Tuantuan Fan; Xin Yao; Zhaoli Sun; Dongling Sang; Li Liu; Huanguang Deng; Yinghao Zhang (Water Research, 2023)

Antibiotic removal and microbial response mechanism in constructed wetlands treating aquaculture wastewater containing veterinary drugs - Yang-yang Deng; Meng-yao Zou; Wen Liu; Ying-li Lian; Qin-mei Guo; Xiao-meng Zhang; Dan A (Journal of Cleaner Production, 2023)

The Key Drivers of Brain Injury by Systemic Inflammatory Responses after Sepsis: Microglia and Neuroinflammation - Yuewen Xin; Mi Tian; Shuixiang Deng; Jiaying Li; Miaoxian Yang; Jianpeng Gao; Xu Pei; Yao Wang; Jiaying Tan; Feng Zhao; Yanqin Gao; Ye Gong (Molecular Neurobiology, 2023)
Sepsis is a leading cause of intensive care unit admission and death worldwide. Most surviving patients show acute or chronic mental disorders, which are known as sepsis-associated encephalopathy (SAE). Although accumulating studies in the past two decades focused on the pathogenesis of SAE, a systematic review of retrospective studies which exclusively focuses on the inflammatory mechanisms of SAE has been lacking yet. This review summarizes the recent advance in the field of neuroinflammation and sheds light on the activation of microglia in SAE. Activation of microglia predominates neuroinflammation. As the gene expression profile changes, microglia show heterogeneous characterizations throughout all stages of SAE. Here, we summarize the systemic inflammation following sepsis and also the relationship of microglial diversity and neuroinflammation. Moreover, a collection of neuroinflammation-related dysfunction has also been reviewed to illustrate the possible mechanisms for SAE. In addition, promising pharmacological or non-pharmacological therapeutic strategies, especially those which target neuroinflammation or microglia, are also concluded in the final part of this review. Collectively, clarification of the vital relationship between neuroinflammation and SAE-related mental disorders would significantly improve our understanding of the pathophysiological mechanisms in SAE and therefore provide potential targets for therapies of SAE aimed at inhibiting neuroinflammation.

Pseudomonas citri sp. nov., a potential novel plant growth promoting bacterium isolated from rhizosphere soil of citrus - Hong Gao; Guang-Da Feng; Zengwei Feng; Qing Yao; Jiali Li; Xiaoqin Deng; Xiaoran Li; Honghui Zhu (Antonie van Leeuwenhoek, 2023)

Nano-mineralogy and growth environment of Fe-Mn polymetallic crusts and nodules from the South China Sea - Yingzhi Ren; Yao Guan; Xiaoming Sun; Li Xu; Zhenglian Xiao; Yuqi Deng; Wentao He (Frontiers in Marine Science, 2023)
Fe-Mn polymetallic crusts and nodules from the South China Sea (SCS) consist of submarine ferromanganese (Fe-Mn) oxide precipitates, and represent important marine mineral resource with substantial economic and scientific research value. Previous studies on the SCS polymetallic crusts and nodules were mainly focused on their bulk mineralogy and geochemistry, whilst research on their nanomineralogy is still lacking. In this study, transmission electron microscopy (TEM), Raman spectroscopic mapping, and in-situ micro X-ray diffraction (XRD) analysis were conducted on the nano-mineralogy of the SCS polymetallic crusts and nodules. It is found that the SCS polymetallic crusts and nodules consist mainly of layered/columnar/mottled nano-phase Fe-Mn minerals and detritus such as quartz, feldspar, and clays. Also, an independent Ti mineral phase has been documented, and the mineralogical analysis reveals the transformation from vernadite to birnessite and todorokite. Titanium forms colloidal minerals in seawater and precipitates into the crusts and nodules with other colloids, such as FeOOH and Si-Al. Vernadite and birnessite can be transformed to todorokite with stable structure under sub-oxic conditions. Therefore, the SCS polymetallic crusts and nodules were formed in a short period of sub-oxic environment and diagenetic process, and the transformation can influence the enrichment of Ni and other metals during the crust/nodule growth.

Spatio-temporal succession of microbial communities in plastisphere and their potentials for plastic degradation in freshwater ecosystems - Lingzhan Miao; Wanyi Li; Tanveer M. Adyel; Yu Yao; Ye Deng; Jun Wu; Yongqiang Zhou; Yue Yu; Jun Hou (Water Research, 2023)

Genome-wide identification of the CsPAL gene family and functional analysis for strengthening green mold resistance in citrus fruit - Linli Wei; Wenjun Wang; Ting Li; Ou Chen; Shixiang Yao; Lili Deng; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Lonp1 and Sig-1R contribute to the counteraction of ursolic acid against ochratoxin A-induced mitochondrial apoptosis - Qipeng Zhang; Wenying Chen; Boyang Zhang; Yiwen Zhang; Yuqing Xiao; Yichen An; Lingyun Han; Huiqiong Deng; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

Multiple essential amino acids regulate mammary metabolism and milk protein synthesis in lactating dairy cows - Jun Zhang; Lu Deng; Xia Zhang; Yangchun Cao; Mengmeng Li; Junhu Yao (Animal Feed Science and Technology, 2023)

Urinary phthalate metabolites and the risk of endometrial polyp: A pilot study from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Wen Yao; Qing-Yun Yao; Yong Huang; Ni-Jie Li; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Yu-Feng Li; et al. (Environmental Pollution, 2023)

Hole transport layer-free carbon-based perovskite solar cells with high-efficiency up to 17.49% in air: From-bottom-to-top perovskite interface modification - Siqi Li; Yao Li; Xiangnan Sun; Yan Li; Fei Deng; Xia Tao (Chemical Engineering Journal, 2023)

Supercooled sugar alcohols stabilized by alkali hydroxides for long-term room-temperature phase change solar-thermal energy storage - Xiaoxiang Li; Jingyi Zhang; Yizhe Liu; Yangzhe Xu; Kehang Cui; Zhenpeng Yao; Benwei Fu; Chengyi Song; Wen Shang; Peng Tao; Tao Deng (Chemical Engineering Journal, 2023)

Visual cues and body volatile β-ocimene are used by the blue tiger butterfly Tirumala limniace to identify conspecifics during courtship - Chengzhe Li; Hua Wang; Xiaoming Chen; Jun Yao; Jianyu Deng (Behavioral Ecology and Sociobiology, 2022)

Protective effects of curcumin against thyroid hormone imbalance after gas explosion-induced traumatic brain injury via activation of the hypothalamic-pituitary-thyroid axis in male rats - Xinwen Dong; Lvfei Deng; Sanqiao Yao; Weidong Wu; Jia Cao; Lei Sun; Yichun Bai; Haibin Li; Xiaogang Weng; Houcheng Ren; Wenjie Ren (Environmental Science and Pollution Research, 2022)

Pore structure characteristics of an underground limestone chamber in the Three Gorges Reservoir area - Yao Xiao; Huafeng Deng; Guanye Li; Meng Peng; Pengfei Xu; Eleyas Assefa; Xingzhou Chen; Lipeng Liu (Bulletin of Engineering Geology and the Environment, 2022)

Molecular characterization of a novel botourmiavirus with inverted complementary termini from the rice blast fungus Magnaporthe oryzae isolate HF04 - Simnin Shuai; Hong Zheng; Hang Ding; Yao Wang; Jinzhe Li; Fuyu Liu; Fengying Liu; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Archives of Virology, 2022)

Microglia-induced autophagic death of neurons via IL-6/STAT3/miR-30d signaling following hypoxia/ischemia - Jun Shu; Xu-Hao Fang; Ya-Jian Li; Yao Deng; Wen-Shi Wei; Li Zhang (Molecular Biology Reports, 2022)

Genetic and transcriptomic dissection of an artificially induced paired spikelets mutant of wheat (Triticum aestivum L.) - Juanyu Zhang; Yanyan Tang; Xi Pu; Xuebing Qiu; Jinhui Wang; Tao Li; Zhao Yang; Yao Zhou; Yuxiao Chang; Junjun Liang; Haili Zhang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2022)

Development of Quercus acutissima (Fagaceae) pollen tubes inside pistils during the sexual reproduction process - Min Deng; Kaiping Yao; Chengcheng Shi; Wen Shao; Qiansheng Li (Planta, 2022)

Identification of nafamostat mesylate as a selective stimulator of NK cell IFN-γ production via metabolism-related compound library screening - Qinglan Yang; Shuju Zhang; Shuting Wu; Baige Yao; Lili Wang; Yana Li; Hongyan Peng; Minghui Huang; Qinghua Bi; Peiwen Xiong; Liping Li; Yafei Deng; et al. (Immunologic Research, 2022)
Natural killer (NK) cells play important roles in controlling virus-infected and malignant cells. The identification of new molecules that can activate NK cells may effectively improve the antiviral and antitumour activities of these cells. In this study, by using a commercially available metabolism-related compound library, we initially screened the capacity of compounds to activate NK cells by determining the ratio of interferon-gamma (IFN-γ) + NK cells by flow cytometry after the incubation of peripheral blood mononuclear cells (PBMCs) with IL-12 or IL-15 for 18 h. Our data showed that eight compounds (nafamostat mesylate (NM), loganin, fluvastatin sodium, atorvastatin calcium, lovastatin, simvastatin, rosuvastatin calcium, and pitavastatin calcium) and three compounds (NM, elesclomol, and simvastatin) increased the proportions of NK cells and CD3 + T cells that expressed IFN-γ among PBMCs cultured with IL-12 and IL-15, respectively. When incubated with enriched NK cells (purity ≥ 80.0%), only NM enhanced NK cell IFN-γ production in the presence of IL-12 or IL-15. When incubated with purified NK cells (purity ≥ 99.0%), NM promoted NK cell IFN-γ secretion in the presence or absence of IL-18. However, NM showed no effect on NK cell cytotoxicity. Collectively, our study identifies NM as a selective stimulator of IFN-γ production by NK cells, providing a new strategy for the prevention and treatment of infection or cancer in select populations.

Seeing Is Believing: Time-Lapse Macro-Imaging of Morphological Changes of Solid Dosages as a Teaching and Research Tool - Li Deng; Yao Fu (Pharmaceutical Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Ribosomal ITS sequence-directed selection for endophytic Myrothecium strains antagonistic to Ralstonia solanacearum to control patchouli bacterial wilt - Wenguang Shi; Jiaqi Li; Huaxiong Yao; Jianbin Li; Meiqi Chen; Danting Chen; Yinghao Fu; Huarong Xie; Zujun Deng (BioControl, 2022)

Composite roof stability control in a short-distance coal seam under goaf: a case study - Yong Li; Xuehua Li; Qiangling Yao; Chuangkai Zheng; Shuai Zou; Liang Deng (Arabian Journal of Geosciences, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Ag3PO4-based photocatalysts and their application in organic-polluted wastewater treatment - Chunmu Yu; Xiaojuan Chen; Ning Li; Yue Zhang; Sailin Li; Jieming Chen; Liang Yao; Kaichun Lin; Yiqi Lai; Xinru Deng (Environmental Science and Pollution Research, 2022)

Spatial matching and flow in supply and demand of water provision services: A case study in Xiangjiang River Basin - Chu-xiong Deng; Da-mei Zhu; Yao-jun Liu; Zhong-wu Li (Journal of Mountain Science, 2022)

Silencing of H19 alleviates oxygen–glucose deprivation/reoxygenation-triggered injury through the regulation of the miR-1306-5p/BCL2L13 axis - Yuxing Huang; Lisha Deng; Lin Zeng; Shanlin Bao; Kun Ye; Chengxun Li; Xiaolin Hou; Yuan Yao; Dingjun Li; Zhen Xiong (Metabolic Brain Disease, 2021)

Rehabilitation of motor function in children with cerebral palsy based on motor imagery - Jiaxin Xie; Lin Jiang; Yanan Li; Baodan Chen; Fali Li; Yuanling Jiang; Dongrui Gao; Lili Deng; XuLin Lv; XianKun Ma; Gang Yin; Dezhong Yao; et al. (Cognitive Neurodynamics, 2021)

Antibiotic Resistance Characterization of Bacteria Isolated from Traditional Chinese Paocai - Mei Li; Yao Tang; Liyan Guo; Tao Lei; Yunfei Deng; Liang Wang; Qisheng Zhang; Chengkang Li (Current Microbiology, 2021)

AddaVax Formulated with PolyI:C as a Potential Adjuvant of MDCK-based Influenza Vaccine Enhances Local, Cellular, and Antibody Protective Immune Response in Mice - Xuanxuan Nian; Jiayou Zhang; Tao Deng; Jing Liu; Zheng Gong; Chuanshuo Lv; Luyao Yao; Junying Li; Shihe Huang; Xiaoming Yang (AAPS PharmSciTech, 2021)
Poor immune responses to inactivated influenza vaccine can be improved by effective and safe adjuvants to increase antibody titers and cellular protective response. In our study, AddaVax and PolyI:C combined adjuvant (AP adjuvant) were used for influenza vaccine development. After immunizing BALB/c mice and Wistar rats intramuscularly, Split inactivated H3N2 vaccine adjuvanted with AP elicited higher serum hemagglutination-inhibition antibodies and IgG titers. We demonstrated that AP induced a transient innate immune cytokines production at the injection site, induced H3N2 uptake by DCs, increased recruitment of monocytes and DCs in LNs, and promoted H3N2 vaccine migration; AP facilitated vaccines to induce a vigorous adaptive immune response. Besides, AP showed good safety as shown by lymph nodes (LNs) size, spleens index of BALB/c mice, and weight changes and C-reaction protein level of BALB/c mice and Wistar rats after repeated administration of high-dose vaccine with or without adjuvant. These findings indicate that AP is a potential novel adjuvant and can be used as a safe and effective adjuvant for MDCK-based influenza inactivated vaccine to induce cellular and antibody protective response.

Structure–activity relationship studies on Pd176252 derivatives leading to discovery of novel GRP receptor antagonist with potent anticancer activity - Ming-jun Yu; Chao Li; Meng He; Yu-ting Zhu; Rui Yang; Sheng-song Deng; Xiao-ming Meng; Ri-sheng Yao (Medicinal Chemistry Research, 2021)

Synergistic degradation of pyrene by Pseudomonas aeruginosa PA06 and Achromobacter sp. AC15 with sodium citrate as the co-metabolic carbon source - Jing Li; Weixin Chen; Wei Zhou; Yao Wang; Maocheng Deng; Shaoqi Zhou (Ecotoxicology, 2021)

Natural Climate Solutions for China: The Last Mile to Carbon Neutrality - Zhangcai Qin; Xi Deng; Bronson Griscom; Yao Huang; Tingting Li; Pete Smith; Wenping Yuan; Wen Zhang (Advances in Atmospheric Sciences, 2021)

Temperature sensitivity of SOM decomposition is linked with a K‐selected microbial community - Hui Li; Shan Yang; Mikhail V. Semenov; Fei Yao; Ji Ye; Rencang Bu; Ruiao Ma; Junjie Lin; Irina Kurganova; Xugao Wang; Ye Deng; Irina Kravchenko; et al. (Global Change Biology, 2021)
Temperature sensitivity (Q 10 ) of soil organic matter (SOM) decomposition is a crucial parameter to predict the fate of soil carbon (C) under global warming. Nonetheless, the response pattern of Q 10 to continuous warming and the underlying mechanisms are still under debate, especially considering the complex interactions between Q 10 , SOM quality, and soil microorganisms. We examined the Q 10 of SOM decomposition across a mean annual temperature (MAT) gradient from −1.9 to 5.1°C in temperate mixed forest ecosystems in parallel with SOM quality and bioavailability, microbial taxonomic composition, and functional genes responsible for organic carbon decomposition. Within this temperature gradient of 7.0°C, the Q 10 values increased with MAT, but decreased with SOM bioavailability. The Q 10 values increased with the prevalence of K‐strategy of soil microbial community, which was characterized by: (i) high ratios of oligotrophic to copiotrophic taxa, (ii) ectomycorrhizal to saprotrophic fungi, (iii) functional genes responsible for degradation of recalcitrant to that of labile C, and (iv) low average 16S rRNA operon copy number. Because the recalcitrant organic matter was mainly utilized by the K‐strategists, these findings independently support the carbon quality‐temperature theory from the perspective of microbial taxonomic composition and functions. A year‐long incubation experiment was performed to determine the response of labile and recalcitrant C pools to warming based on the two‐pool model. The decomposition of recalcitrant SOM was more sensitive to increased temperature in southern warm regions, which might attribute to the dominance of K‐selected microbial communities. It implies that climate warming would mobilize the larger recalcitrant pools in warm regions, exacerbating the positive feedback between increased MAT and CO 2 efflux. This is the first attempt to link temperature sensitivity of SOM decomposition with microbial eco‐strategies by incorporating the genetic information and disentangling the complex relationship between Q 10 and soil microorganisms.

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The dynamics in rhizosphere microbial communities under bacterial wilt resistance by mulberry genotypes - Zhaoxia Dong; Yao Guo; Cui Yu; Zhu Zhixian; Mo Rongli; Wen Deng; Yong Li; Xingming Hu (Archives of Microbiology, 2021)

Fatigue Characteristic of Designed T-Type Specimen under Two-Step Repeating Variable Amplitude Load with Low-Amplitude Load below the Fatigue Limit - Jin Gan; Di Sun; Hui Deng; Zhou Wang; Xiaoli Wang; Li Yao; Weiguo Wu (Journal of Marine Science and Engineering, 2021)
In order to investigate the non-linear fatigue cumulative damage of joints in ocean structural parts, one type of low carbon steel Q345D was employed to prepare designed T-type specimens, and a series of fatigue experiments were carried out on the specimens under two-step repeating variable amplitude loading condition. The chosen high cyclic loads were larger than the constant amplitude fatigue limit (CAFL) and the chosen low cyclic loads were below the CAFL. Firstly, the S-N curve of designed T-type specimen was obtained via different constant amplitude fatigue tests. Then, a series of two-step repeating variable load were carried out on designed T-type specimens with the aim of calculating the cumulative damage of specimen under the variable fatigue load. The discussions about non-linear fatigue cumulative damage of designed T-type specimens and the interaction effect between the high and low amplitude loadings on the fatigue life were carried out, and some meaningful conclusions were obtained according to the series of fatigue tests. The results show that fatigue cumulative damage of designed T-type specimens calculated based on Miner’s rule ranges from 0.513 to 1.756. Under the same cycle ratio, the cumulative damage increases with the increase of high cyclic stress, and at the same stress ratio, the cumulative damage increases linearly with the increase of cycle ratio. Based on the non-linear damage evaluation method, it is found that the load interaction effect between high and low stress loads exhibits different damage or strengthening effects with the change of stress ratio and cycle ratio.

Construction and characterization of UAA-controlled recombinant Zika virus by genetic code expansion - Rong-Rong Zhang; Qing Ye; Xiao-Feng Li; Yong-Qiang Deng; Yan-Peng Xu; Xing-Yao Huang; Qing Xia; Cheng-Feng Qin (Science China Life Sciences, 2021)

Geochemical, mineralogical and chronological studies of mafic-intermediate dykes in the Jiaodong Peninsula: implications for Late Mesozoic mantle source metasomatism and lithospheric thinning of the eastern North China Craton - Xuefei Liu; Jun Deng; Yayun Liang; Qingfei Wang; Gongjian Li; Yao Ma; Lijuan Xu; Yinghuai Lu (International Geology Review, 2020)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Biological denitrification in a macrophytic lake: implications for macrophytes-dominated lake management in the north of China - Huan-guang Deng; Ju Zhang; Jin-jia Wu; Xin Yao; Li-wei Yang (Environmental Science and Pollution Research, 2020)

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

Overexpression of PREX1 in oral squamous cell carcinoma indicates poor prognosis - Shu-Cheng Wan; Hao Wu; Hao Li; Wei-Wei Deng; Yao Xiao; Cong-Cong Wu; Lei-Lei Yang; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2020)

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Variation of biogeochemical cycle of riverine dissolved inorganic carbon and silicon with the cascade damming - Haojun Deng; Zhen Tao; Quanzhou Gao; Ling Yao; Yong Feng; Yinhua Li; Jian Ding; Zhengang Wang; Xiaoxi Lyu; Peng Xu (Environmental Science and Pollution Research, 2020)

The degradation effect and mechanism by water-rock interaction in the layered sandstone in the Three Gorges reservoir area - Qiao Jiang; Huafeng Deng; Jianlin Li; Zuosen Luo; Eleyas Assefa; Jingcheng Fang; Yao Xiao (Arabian Journal of Geosciences, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Branched-chain amino acids regulate plant growth by affecting the homeostasis of mineral elements in rice - Cheng Jin; Yangyang Sun; Yuheng Shi; Yuanyuan Zhang; Kai Chen; Yuan Li; Guige Liu; Fang Yao; Deng Cheng; Jie Li; Junjie Zhou; Lianghuan Qu; et al. (Science China Life Sciences, 2019)

Altitudinal variation in body size in Bufo minshanicus supports Bergmann’s rule - Tong Lei Yu; Dong Li Wang; Michael Busam; Yao Hui Deng (Evolutionary Ecology, 2019)

Registrating large mismatching SAR images based on corners and surface extremum strategy - Guobiao Yao; Li Zhang; Tongguang Shi; Kazhong Deng (International Journal of Remote Sensing, 2019)

Multiplex QTL editing of grain-related genes improves yield in elite rice varieties - Jianping Zhou; Xuhui Xin; Yao He; Hongqiao Chen; Qian Li; Xu Tang; Zhaohui Zhong; Kejun Deng; Xuelian Zheng; Sayed Abdul Akher; Guangze Cai; Yiping Qi; et al. (Plant Cell Reports, 2019)

Beauveria bassiana infection reduces the vectorial capacity of Aedes albopictus for the Zika virus - Shengqun Deng; Qiang Huang; Haixia Wei; Lijuan Zhou; Lijie Yao; Dongliang Li; Shuizhen Wu; Jiating Chen; Hongjuan Peng (Journal of Pest Science, 2019)

Abnormal intrinsic cerebro-cerebellar functional connectivity in un-medicated patients with bipolar disorder and major depressive disorder - Yuan He; Ying Wang; Ting-Ting Chang; Yanbin Jia; Junjing Wang; Shuming Zhong; Huiyuan Huang; Yao Sun; Feng Deng; Xiaoyan Wu; Chen Niu; Li Huang; et al. (Psychopharmacology, 2018)

Selection and validation of reference genes for reverse transcription quantitative real-time PCR (RT-qPCR) in silkworm infected with Bombyx mori bidensovirus - Zhaoyang Hu; Yanchun Deng; Xiaolong Zhang; Peipei Tang; Weijuan Sun; Guohui Li; Qian Yu; Qin Yao (Biologia, 2018)

Over-expression of IQGAP1 indicates poor prognosis in head and neck squamous cell carcinoma - Cong-Cong Wu; Hao Li; Yao Xiao; Lei-Lei Yang; Lei Chen; Wei-Wei Deng; Lei Wu; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2018)

Effect of water cadmium concentration and water level on the growth performance of Salix triandroides cuttings - Xin Yao; Fengfeng Ma; Youzhi Li; Xiaohui Ding; Dongsheng Zou; Yandong Niu; Hualin Bian; Jiajun Deng (Environmental Science and Pollution Research, 2018)

The Arc Gene Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Rui Bi; Li-Li Kong; Min Xu; Guo-Dong Li; Deng-Feng Zhang; Tao Li; Yiru Fang; Chen Zhang; Buchang Zhang; Yong-Gang Yao (Molecular Neurobiology, 2018)

Pterostilbene Attenuates Early Brain Injury Following Subarachnoid Hemorrhage via Inhibition of the NLRP3 Inflammasome and Nox2-Related Oxidative Stress - Haixiao Liu; Lei Zhao; Liang Yue; Bodong Wang; Xia Li; Hao Guo; Yihui Ma; Chen Yao; Li Gao; Jianping Deng; Lihong Li; Dayun Feng; et al. (Molecular Neurobiology, 2017)

Methane alleviates carbon tetrachloride induced liver injury in mice: anti-inflammatory action demonstrated by increased PI3K/Akt/GSK-3β-mediated IL-10 expression - Ying Yao; Liping Wang; Peipei Jin; Na Li; Yan Meng; Changli Wang; Mengda Xu; Yan Zhang; Jinjun Bian; Xiaoming Deng (Journal of Molecular Histology, 2017)

Acclimation of Salix triandroides cuttings to incomplete submergence is reduced by low light - Xiaohui Ding; Jianfeng Zou; Youzhi Li; Xin Yao; Dongsheng Zou; Canming Zhang; Nan Yang; Yandong Niu; Hualin Bian; Jiajun Deng; Zixuan Ge (Aquatic Ecology, 2017)

Enhanced Procoagulant Activity on Blood Cells after Acute Ischemic Stroke - Zhipeng Yao; Lixiu Wang; Xiaoming Wu; Lu Zhao; Chunling Chi; Li Guo; Dongxia Tong; Xiaoyan Yang; Zengxiang Dong; Ruijuan Deng; Valerie A. Novakovic; Hemant S Thatte; et al. (Translational Stroke Research, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

Population structure and diversity of citrus tristeza virus (CTV) isolates in Hunan province, China - Cui Xiao; Run-Xian Yao; Fang Li; Su-Ming Dai; Grazia Licciardello; Antonino Catara; Alessandra Gentile; Zi-Niu Deng (Archives of Virology, 2017)

Reactive oxygen species and hormone signaling cascades in endophytic bacterium induced essential oil accumulation in Atractylodes lancea - Jia-Yu Zhou; Xia Li; Dan Zhao; Meng-Yao Deng-Wang; Chuan-Chao Dai (Planta, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Inhibitory effect of Gardenblue blueberry (Vaccinium ashei Reade) anthocyanin extracts on lipopolysaccharide-stimulated inflammatory response in RAW 264.7 cells - Wei Xu; Qing Zhou; Yong Yao; Xing Li; Jiu-liang Zhang; Guan-hua Su; Ai-ping Deng (Journal of Zhejiang University-SCIENCE B, 2016)

Co-expression of MtDREB1C and RcXET Enhances Stress Tolerance of Transgenic China Rose (Rosa chinensis Jacq.) - Ji-Ren Chen; Yan-Bin Chen; Monika Ziemiańska; Rong Liu; Zi-Niu Deng; Irena Niedźwiecka-Filipiak; Yan-Lin Li; Jin-Xia Jiao; Xing-Yao Xiong (Journal of Plant Growth Regulation, 2016)

Clinical and pathological significance of N-Myc downstream-regulated gene 2 (NDRG2) in diverse human cancers - Wei Hu; Yang Yang; Chongxi Fan; Zhiqiang Ma; Chao Deng; Tian Li; Jianjun Lv; Weiwei Yao; Jianyuan Gao (Apoptosis, 2016)

Erratum to: The Clinical Utility of TIMP3 Expression in ACTH-Secreting Pituitary Tumor - Bowen Sun; Xiaohai Liu; Yakun Yang; Congxin Dai; Ying Li; Yonghui Jiao; Zhenqing Wei; Yong Yao; Ming Feng; Xinjie Bao; Kan Deng; Ning Wang; et al. (Journal of Molecular Neuroscience, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

Effects of surfactants on low-molecular-weight organic acids to wash soil zinc - Yue Chen; Shirong Zhang; Xiaoxun Xu; Ping Yao; Ting Li; Guiyin Wang; Guoshu Gong; Yun Li; Ouping Deng (Environmental Science and Pollution Research, 2016)

An Empirical Method to Investigate the Spatial and Temporal Distribution of Annual Average Groundwater Recharge Intensity-a Case Study in Grand River, Michigan, USA - Zhang Jing; Lan-yue Zhang; Qin Xie; Yao Li; Shi-huai Deng; Fei Shen; Yuan-wei Li; Hong Xiao; Gang Yang; Chun Song (Water Resources Management, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

The Clinical Utility of TIMP3 Expression in ACTH-Secreting Pituitary Tumor - Bowen Sun; Xiaohai Liu; Yakun Yang; Congxin Dai; Ying Li; Yonghui Jiao; Zhenqing Wei; Yong Yao; Ming Feng; Xinjie Bao; Kan Deng; Ning Wang; et al. (Journal of Molecular Neuroscience, 2016)

Paleogeographic framework and provenance features during Late Triassic Chang 9 time of the Yanchang Formation, Ordos Basin, China - Xiong Ding; Jingchun Tian; Jingshan Chen; Jingli Yao; Xiuqin Deng; Yuanhao Li (Arabian Journal of Geosciences, 2015)

SecReT6 : a web‐based resource for type VI secretion systems found in bacteria - Jun Li; Yufeng Yao; H. Howard Xu; Limin Hao; Zixin Deng; Kumar Rajakumar; Hong‐Yu Ou (Environmental Microbiology, 2015)
Summary SecReT6 ( http://db‐mml.sjtu.edu.cn/SecReT6/ ) is an integrated database providing comprehensive information on type VI secretion systems ( T6SSs ) in bacteria. T6SSs are a class of sophisticated cell contact‐dependent apparatuses involved in mediating antagonistic or synergistic communications between bacteria and/or bacteria and eukaryotes. These apparatuses have recently been found to be widely distributed among G ram‐negative bacterial species. SecReT6 offers a unique, readily explorable archive of known and putative T6SSs , and cognate effectors found in bacteria. It currently contains data on 11 167 core T6SS components mapping to 906 T6SSs found in 498 bacterial strains representing 240 species, as well as a collection of over 600 directly relevant references. Also collated and archived were 1340 diverse candidate secreted effectors which were experimentally shown and/or predicted to be delivered by T6SSs into target eukaryotic and/or prokaryotic cells as well as 196 immunity proteins. A broad range of T6SS gene cluster detection and comparative analysis tools are readily accessible via SecReT6 , which may aid identification of effectors and immunity proteins around the T6SS core components. This database will be regularly updated to ensure its ongoing maximal utility and relevance to the scientific research community.

Apolipoprotein E gene polymorphisms associated with processing speed and executive functions in healthy Han Chinese - Cheng-Cheng Zhang; Hong-Yan Ren; Ming-Li Li; Qiang Wang; Wei Deng; Wan-Jun Guo; Wei Lei; Bo Xiang; Lian-Sheng Zhao; Xiao-Hong Ma; Yong-Gang Yao; Tao Li (Neuroscience Bulletin, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Common variants of the PINK1 and PARL genes do not confer genetic susceptibility to schizophrenia in Han Chinese - Xiao Li; Wen Zhang; Chen Zhang; Zhenghui Yi; Deng-Feng Zhang; Wei Gong; Jinsong Tang; Dong Wang; Weihong Lu; Xiaogang Chen; Yiru Fang; Yong-Gang Yao (Molecular Genetics and Genomics, 2015)

Phosphate enhances uptake of As species in garland chrysanthemum (C. coronarium) applied with chicken manure bearing roxarsone and its metabolites - Lixian Yao; Lianxi Huang; Zhaohuan He; Changming Zhou; Guoliang Li; Xiancai Deng (Environmental Science and Pollution Research, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

Distribution of enterovirus 71 RNA in inflammatory cells infiltrating different tissues in fatal cases of hand, foot, and mouth disease - Pin Yu; Zifen Gao; Yuanyuan Zong; Linlin Bao; Lili Xu; Wei Deng; Yanfeng Xu; Zhancheng Gao; Yanfeng Yao; Fengdi Li; Qi Lv; Chuan Qin (Archives of Virology, 2015)

HPLC pigment profiles of 31 harmful algal bloom species isolated from the coastal sea areas of China - Shuxia Liu; Peng Yao; Zhigang Yu; Dong Li; Chunmei Deng; Yu Zhen (Journal of Ocean University of China, 2014)

Interferon-γ produced by tumor-infiltrating NK cells and CD4+ T cells downregulates TNFSF15 expression in vascular endothelial cells - Yi Lu; Xin Gu; Li Chen; Zhi Yao; Juan Song; Xiulong Niu; Rong Xiang; Tao Cheng; Zhihai Qin; Weimin Deng; Lu-Yuan Li (Angiogenesis, 2014)

Genetic variants of complement genes Ficolin-2, Mannose-binding lectin and Complement factor H are associated with leprosy in Han Chinese from Southwest China - Deng-Feng Zhang; Xian-Qiong Huang; Dong Wang; Yu-Ye Li; Yong-Gang Yao (Human Genetics, 2013)

Population genetics of wild Hizikia fusiformis (Sargassaceae, Phaeophyta) along China’s coast - Shenhui Yu; Yunyan Deng; Jianting Yao; Shengyao Li; Xin Xin; Delin Duan (Journal of Applied Phycology, 2012)

Dynamic sieving capillary electrophoresis analysis of xylitol selenite-induced apoptosis in SMMC-7221 cells - Ming Lei; Didi Chen; Xiaojie Deng; Jing Liu; Layue Chen; Yanli Liu; Bing Li; Hancao Yao; Guomei Xiong; Yu Cao; Jihong Yang; Chao Qi (Biotechnology Letters, 2012)

Genetic variants of the MRC1 gene and the IFNG gene are associated with leprosy in Han Chinese from Southwest China - Dong Wang; Jia-Qi Feng; Yu-Ye Li; Deng-Feng Zhang; Xiao-An Li; Qing-Wei Li; Yong-Gang Yao (Human Genetics, 2012)

Isolation and characterization of sixteen microsatellite loci of a blind cavefish, Triplophysa xiangxiensis - Yanhong Yao; Deng Qiang Wang; Li He; Lai Ning Yu (Conservation Genetics Resources, 2012)

Quantitative assessment of the effect of MTHFR polymorphisms on the risk of lung carcinoma - Yao Zhang; Guo Qiang Chen; Yong Ji; Bin Huang; Wei Sheng Shen; Li Chun Deng; Lei Xi; Xiang Ming Cao (Molecular Biology Reports, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Down-modulation of TNFSF15 in ovarian cancer by VEGF and MCP-1 is a pre-requisite for tumor neovascularization - Weimin Deng; Xin Gu; Yi Lu; Chao Gu; Yangyang Zheng; Zhisong Zhang; Li Chen; Zhi Yao; Lu-Yuan Li (Angiogenesis, 2012)

PtSVP, an SVP homolog from trifoliate orange (Poncirus trifoliata L. Raf.), shows seasonal periodicity of meristem determination and affects flower development in transgenic Arabidopsis and tobacco plants - Zhi-Min Li; Jin-Zhi Zhang; Li Mei; Xiu-Xin Deng; Chun-Gen Hu; Jia-Ling Yao (Plant Molecular Biology, 2010)

Znrg, a novel gene expressed mainly in the developing notochord of zebrafish - Yaping Zhou; Yan Xu; Jianzhen Li; Yao Liu; Zhe Zhang; Fengjiao Deng (Molecular Biology Reports, 2010)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Influence of ginsenoside Rg1, a panaxatriol saponin from Panax notoginseng, on renal fibrosis in rats with unilateral ureteral obstruction - Xi-sheng Xie; Man Yang; Heng-cuang Liu; Chuan Zuo; Zi Li; Yao Deng; Jun-ming Fan (Journal of Zhejiang University-SCIENCE B, 2008)

Expression analysis of the NDRG2 gene in mouse embryonic and adult tissues - Xiao-Lan Hu; Xin-Ping Liu; Yan-Chun Deng; Shu-Xin Lin; Lin Wu; Jian Zhang; Li-Feng Wang; Xiao-Bin Wang; Xia Li; Lan Shen; Yuan-Qiang Zhang; Li-Bo Yao (Cell and Tissue Research, 2006)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)